Double-sided adhesive sheet

By introducing an intermediate layer with a total thickness of less than 60 μm into the double-sided adhesive sheet, and using water dispersed materials to improve Young's modulus, the compromise between processability and impact resistance of the double-sided adhesive sheet in the prior art is solved. The problem has achieved efficient and balanced results.

CN119403895APending Publication Date: 2025-02-07NITTO DENKO CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380048862.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-27
Filing Date
2023-06-22
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

When the existing double-sided adhesive sheets take into account both processability and impact resistance, especially in portable electronic devices that are thinner and lighter, it is difficult to meet these requirements at the same time, resulting in unfavorable processability and insufficient impact resistance.

Method used

A double-sided adhesive sheet having a total thickness of 60 μm or less is used, which consists of a first adhesive layer, an intermediate layer of at least one layer and a second adhesive layer. The intermediate layer is formed of a water dispersed material, and the Young's modulus is in the range of 1.5 to 1500 MPa, which prevents the migration of interlayer components and improves the processability and impact resistance of the adhesive sheet.

Benefits of technology

It realizes the processing and impact resistance in thin double-sided adhesive sheets, improves the overall performance of the adhesive sheets, and makes it suitable for thin and lightweight applications such as portable electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403895A_ABST
    Figure CN119403895A_ABST
Patent Text Reader

Abstract

Provided is a thin double-sided adhesive sheet capable of achieving both processability and impact resistance. Provided is a double-sided pressure-sensitive adhesive sheet having a first pressure-sensitive adhesive layer, at least one intermediate layer, and a second pressure-sensitive adhesive layer in this order. The total thickness of the double-sided adhesive sheet is 60 [mu] m or less. In addition, the thickness ratio of the intermediate layer relative to the total thickness is within the range of 10%-60%. Further, the intermediate layer is formed of a water-dispersed material. The Young's modulus of the intermediate layer is in the range of 1.5 to 1500 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a double-sided adhesive sheet.

[0002] This application claims priority based on Japanese Patent Application No. 2022-102832 filed on June 27, 2022, the entire contents of which are incorporated into this specification as a reference. Background Art

[0003] Generally, adhesives (also called pressure-sensitive adhesives. The same applies hereinafter) are in a soft solid (viscoelastic) state in a temperature range near room temperature, and have the property of being easily bonded to an adherend by pressure. Taking advantage of such properties, adhesives are widely used, for example, in the form of double-sided adhesive tapes with a substrate having an adhesive layer on a supporting substrate, for the purpose of joining and fixing components in portable electronic devices such as smartphones. As technical documents on double-sided adhesive tapes with a substrate, Patent Documents 1 to 5 can be cited.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2018 / 101335

[0007] Patent Document 2: Japanese Patent Application Publication No. 2000-248236

[0008] Patent Document 3: Japanese Patent Publication No. 2009-536675

[0009] Patent Document 4: Japanese Patent Application Publication No. 2017-105878

[0010] Patent Document 5: Japanese Patent Application Publication No. 2006-63189 Summary of the invention

[0011] Problem that the invention aims to solve

[0012] In the double-sided adhesive sheet (double-sided adhesive sheet), in order to obtain good processability, polyethylene terephthalate (PET) film is usually used as a supporting substrate. However, the adhesive sheet with a PET supporting substrate has a tendency to reduce impact resistance and concave-convex followability due to the high elastic modulus of PET. On the other hand, according to the difference in the application position of the adhesive sheet used in the portable electronic device with the danger of falling, etc., the impact resistance will be required. In order to obtain good impact resistance, it is preferred to use a so-called substrate-free adhesive sheet without a supporting substrate, but the substrate-free adhesive sheet is only composed of an adhesive layer of a viscoelastic body in essence, so it is disadvantageous in processability compared with the adhesive sheet with a substrate. For example, the adhesive sheet used in the fixing of the components of a portable electronic device is processed into a shape suitable for the bonding and fixing part by implementing a cutting process such as a punching process, but the substrate-free adhesive sheet will be attached to the blade during the continuous punching process, and it is easy to produce unfavorable conditions such as punching the adhesive sheet supplied next when processing compared with the adhesive sheet with a substrate.

[0013] As described above, in order to take into account both processability and impact resistance, which are technically in a compromise relationship, the following means can be used, for example: increasing the thickness of the adhesive layer provided on both sides of the PET support substrate to obtain the elastic modulus of the support substrate, and utilizing the stress relaxation caused by the adhesive layer. However, for example, adhesive sheets used in portable electronic devices tend to be thinner due to the requirements of miniaturization and lightweight of portable electronic devices, and the method of utilizing the thickness of the adhesive layer is limited. In thin adhesive sheets, it is more difficult to take into account both processability and impact resistance.

[0014] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a thin double-sided PSA sheet that can achieve both processability and impact resistance.

[0015] Solutions for solving problems

[0016] According to the specification, a double-sided adhesive sheet is provided, which has a first adhesive layer, at least one intermediate layer and a second adhesive layer in sequence. The total thickness of the double-sided adhesive sheet is 60 μm or less. In addition, relative to the total thickness, the thickness ratio of the intermediate layer is in the range of 10% to 60%. Further, the intermediate layer is formed by a water-dispersible material. And the Young's modulus of the intermediate layer is in the range of 1.5 to 1500 MPa. According to the above-mentioned structure, although the double-sided adhesive sheet is a thin double-sided adhesive sheet with a total thickness of less than 60 μm, it is also possible to take into account both processability and impact resistance.

[0017] It should be noted that by using a water-dispersible material (specifically, an aqueous dispersion of an intermediate layer forming material such as a polymer) as an intermediate layer forming material, it is possible to prevent or suppress the migration of components that may occur between the adhesive layer. Less interlayer component migration means that it is not easy to produce the characteristic changes of the adhesive sheet over time caused by the migration of the component. In the thin adhesive sheet disclosed herein with a total thickness of less than 60 μm, even a small amount of component migration is likely to increase the influence on various characteristics such as adhesive properties. Therefore, preventing or suppressing interlayer component migration is important in practical applications.

[0018] In some preferred embodiments, the storage modulus of the intermediate layer at a temperature of 25°C and a frequency of 160 Hz is 7.0×10 6 ~5.0×10 9 Pa. The above frequency is considered to correspond to the speed range during punching. By using an intermediate layer having a storage elastic modulus at the above frequency of 160 Hz as the intermediate layer, good processability (specifically, punching processability) is easily obtained.

[0019] In some preferred embodiments, the storage modulus of the intermediate layer at a temperature of 25°C and a frequency of 1000 to 10000 Hz is 3.7×10 9 Pa or less. It is considered that the above frequency range corresponds to the velocity range of the impact (for example, the impact in the impact resistance test described later, such as the drop impact). 3 ~10 4 The intermediate layer with a storage modulus of 100 Hz is used as the intermediate layer, which is easy to obtain good impact resistance.

[0020] In some preferred embodiments, the intermediate layer comprises polyurethane resin, rubber, polyolefin resin, acrylic resin or a blend thereof. According to the configuration of the intermediate layer using the above materials, both processability and impact resistance can be preferably achieved.

[0021] In some preferred embodiments, the first adhesive layer and the second adhesive layer are both formed by a water-dispersible adhesive composition. The water-dispersible adhesive layer composition requires time and effort in the high-precision coating of a thin layer of adhesive due to the coating properties on a substrate (e.g., a PET substrate). In the technology disclosed herein, a design that focuses on preventing the migration of interlayer components over time can be adopted by forming the first adhesive layer and the second adhesive layer by a water-dispersible adhesive composition.

[0022] In some preferred embodiments, the first adhesive layer and the second adhesive layer are both acrylic adhesive layers containing acrylic polymers. In the technology disclosed herein, it is preferably implemented in a manner using an acrylic adhesive. As the acrylic polymer, from the viewpoint of impact resistance, an acrylic polymer having a glass transition temperature (Tg) of -25°C or less is preferably used.

[0023] Some preferred embodiments of the double-sided PSA sheet have a 180-degree peel strength of 6 N / 20 mm or more relative to a stainless steel plate. Double-sided PSA sheets having such a peel strength relative to a SUS plate are preferably used as a bonding and fixing means with high bonding reliability in various applications.

[0024] In the double-sided adhesive sheet disclosed herein, since it is thin and can take into account both processability and impact resistance, it has a tendency to be miniaturized and lightweight, and is preferably used for joining components of portable electronic devices that require good processability and impact resistance. After the double-sided adhesive sheet disclosed herein is formed into a predetermined shape such as a strip or a frame by punching and other processing, it is used for joining components of portable electronic devices, and can exert good impact resistance to the falling of portable electronic devices. As described above, according to this specification, a portable electronic device using any double-sided adhesive sheet disclosed herein can be provided, in other words, a portable electronic device containing the adhesive sheet is provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic cross-sectional view showing the structure of a pressure-sensitive adhesive sheet according to one embodiment. DETAILED DESCRIPTION

[0026] The following describes a suitable embodiment of the present invention. It should be noted that, for matters necessary for the implementation of the present invention other than matters specifically mentioned in this specification, those skilled in the art can understand based on the teachings of the implementation of the invention recorded in this specification and the common knowledge at the time of application. The present invention can be implemented based on the contents disclosed in this specification and the common knowledge in the art. In addition, in the following drawings, the same symbols are sometimes used to illustrate components and parts that play the same role, and repeated descriptions are sometimes omitted or simplified. In addition, the embodiments described in the drawings are schematically illustrated in order to clearly illustrate the present invention, and do not necessarily accurately represent the size and scale of the actual product provided.

[0027] In this specification, "adhesive" refers to a material that is in a soft solid (viscoelastic) state in a temperature range near room temperature and has the property of being bonded to an adherend by pressure. The adhesive referred to here is defined in "CADahlquist, "Adhesion: Fundamentals and Practice", McLaren & Sons, (1966) P.143". Generally speaking, it can be a material that satisfies the complex tensile modulus E*(1Hz)<10 7 dyne / cm 2 A material having the above properties at 25°C.

[0028] In this specification, "(meth)acryloyl" means both acryloyl and methacryloyl. Similarly, "(meth)acrylate" means both acrylate and methacrylate, and "(meth)acrylic acid" means both acrylic acid and methacrylic acid.

[0029] In this specification, "acrylic polymer" refers to a polymer containing more than 50% by weight of monomer units derived from acrylic monomers as monomer units constituting the polymer. The acrylic monomers are monomers having at least one (meth)acryloyl group in one molecule.

[0030] In this specification, "water-dispersible" refers to a state in which at least a part of the components are dispersed in water. For example, "water-dispersible adhesive composition" refers to a composition containing an adhesive composition and water, and at least a part of the adhesive composition is dispersed in water. Water-dispersible also includes a suspended state and an emulsified state.

[0031] <Composition of Double-Sided PSA Sheet>

[0032] The double-sided adhesive sheet disclosed herein has the first adhesive layer, the middle layer and the second adhesive layer in sequence. The concept of the adhesive sheet described herein may include adhesive sheets referred to as adhesive tapes, adhesive labels, adhesive films, etc. It should be noted that the above-mentioned adhesive layer is typically formed continuously, but is not limited to this form, for example, it may also be an adhesive layer forming regular or irregular patterns such as dot-shaped and striped. In addition, the adhesive sheet may be in a roll shape or in a monolithic shape. Alternatively, it may also be an adhesive sheet further processed into a form of various shapes.

[0033] The adhesive sheet disclosed herein may be, for example, Figure 1The double-sided adhesive sheet 1 schematically shows a cross-sectional structure. The double-sided adhesive sheet 1 comprises an intermediate layer 15 and a first adhesive layer 11 and a second adhesive layer 12 supported by both sides of the intermediate layer 15. More specifically, the first adhesive layer 11 and the second adhesive layer 12 are provided on the first surface 15A and the second surface 15B (both of which are non-peelable) of the intermediate layer 15, respectively. Figure 1 As shown, the double-sided adhesive sheet 1 before use (before being pasted on the adherend) can be a form that overlaps with a release liner 21 whose front side 21A and back side 21B are both release surfaces and is wound into a spiral shape. In the double-sided adhesive sheet 1 of the form, the surface of the second adhesive layer 12 (the second adhesive surface 12A) is protected by the front side 21A of the release liner 21, and the surface of the first adhesive layer 11 (the first adhesive surface 11A) is protected by the back side 21B of the release liner 21. Alternatively, it can also be a form in which the first adhesive surface 11A and the second adhesive surface 12A are protected by two independent release liners, respectively.

[0034] The total thickness (including adhesive layer and intermediate layer, but excluding release liner) of the double-sided adhesive sheet disclosed herein is less than 60 μm. The double-sided adhesive sheet with a total thickness limited to less than 60 μm can well cope with the thinning and lightweight requirements of products (such as portable electronic devices) to which the double-sided adhesive sheet is applied. In some preferred embodiments, from the viewpoint of thinning, the total thickness of the double-sided adhesive sheet is less than about 50 μm, can be less than about 45 μm, can be less than about 40 μm, or can be less than about 35 μm (for example, less than 32 μm). In other embodiments, the total thickness of the double-sided adhesive sheet can be less than about 30 μm, can be less than about 25 μm, or can be less than about 22 μm. According to the technology disclosed herein, in the structure where the total thickness of the double-sided adhesive sheet is limited as described above, by setting the thickness ratio of the intermediate layer to a specified range, good processability can be obtained and excellent impact resistance can be achieved. The lower limit of the total thickness of the double-sided adhesive sheet is not particularly limited, for example, it can be about 5 μm or more, and it is appropriate to set it to about 10 μm or more, preferably about 15 μm or more, more preferably about 20 μm or more, and further preferably about 25 μm or more, and can be about 30 μm or more, or about 40 μm or more. According to the technology disclosed herein, the double-sided adhesive sheet having a total thickness within the above range has good adhesive properties and can take into account both processability and impact resistance at a high level.

[0035] <First Adhesive Layer and Second Adhesive Layer>

[0036] (Base polymer)

[0037] In the technology disclosed herein, the kind of the adhesive constituting the 1st adhesive layer and the 2nd adhesive layer is not particularly limited. The above-mentioned adhesive can comprise one or more than two kinds of various rubber-like polymers such as acrylic acid polymer, rubber polymer (natural rubber, synthetic rubber, their mixture etc.), polyester polymer, urethane polymer, polyether polymer, organosilicon polymer, polyamide polymer, fluorine polymer that can be used in the field of adhesive as adhesive as a bonding polymer (hereinafter also referred to as " base polymer "). From the viewpoints such as bonding performance, cost, it is possible to preferably adopt the adhesive comprising acrylic acid polymer or rubber polymer as base polymer. Wherein, preferably the adhesive (acrylic acid adhesive) of base polymer with acrylic acid polymer. The technology disclosed herein is preferably implemented in the mode of using acrylic acid adhesive.

[0038] Hereinafter, the PSA layer composed of an acrylic PSA, that is, the PSA sheet having an acrylic PSA layer will be mainly described, but the PSA layer of the PSA sheet disclosed herein is not intended to be limited to the PSA layer composed of an acrylic PSA.

[0039] It should be noted that the "base polymer" of the adhesive refers to the main component of the rubbery polymer contained in the adhesive, and there is no other limiting explanation. The above-mentioned rubbery polymer refers to a polymer that shows rubber elasticity in a temperature range near room temperature. In addition, in this manual, unless otherwise specified, the "main component" refers to a component whose content exceeds 50% by weight.

[0040] (Acrylic polymer)

[0041] In some preferred embodiments, the pressure-sensitive adhesive layer (hereinafter referred to as including the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer, unless otherwise specified) contains an acrylic polymer as a base polymer.

[0042] As the acrylic polymer, for example, a polymer containing a (meth)acrylic acid alkyl ester as a main monomer and a monomer raw material (monomer component) that may further contain a secondary monomer copolymerizable with the main monomer is preferred. Here, the main monomer refers to a component that occupies more than 50% by weight of the monomer composition in the above-mentioned monomer raw material.

[0043] As the (meth)acrylic acid alkyl ester, for example, a compound represented by the following formula (1) can be preferably used.

[0044] CH2=C(R 1 )COOR 2 (1)

[0045] Here, R in the above formula (1) 1 is a hydrogen atom or a methyl group.2 is a chain alkyl group having 1 to 20 carbon atoms (hereinafter, this range of carbon atoms may be referred to as "C 1-20 From the viewpoint of storage modulus of the adhesive, R 2 C 1-14 Alkyl (meth)acrylates having a chain alkyl group, preferably R 2 C 1-10 (meth)acrylates having a chain alkyl group, particularly preferably R 2 It is a butyl or 2-ethylhexyl alkyl (meth)acrylate.

[0046] As R 2 C 1-20 Examples of the alkyl (meth)acrylate having a chain alkyl group thereof include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. These alkyl (meth)acrylates may be used alone or in combination of two or more. Preferred alkyl (meth)acrylates include n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA).

[0047] The technology disclosed herein can be preferably implemented in the following manner: the monomer component comprises R of the above formula (1) 2 C 4-10 The (meth)acrylic acid alkyl ester having a chain alkyl group (typically at least one of BA and 2EHA), and the (meth)acrylic acid alkyl ester contained in the monomer component has R of the above formula (1) 2 C 4-10 Alkyl (meth)acrylate of chain alkyl 4-10 The total amount of the (meth)acrylic acid C (meth)acrylic acid C is 70% by weight or more (typically 80% by weight or more). 4-10In the embodiment of the chain alkyl ester, the ratio of 2EHA is not particularly limited. 4-10 In the case of linear alkyl esters, more than 50 wt % is appropriate, and from the viewpoint of impact resistance, it is preferably 70 wt % or more, more preferably 90 wt % or more, and even more preferably 95 wt % or more (eg, 95 to 100 wt %).

[0048] The above-mentioned alkyl (meth)acrylate comprises R 2 C 4-10 In the case of an alkyl (meth)acrylate having a chain alkyl group (typically at least one of BA and 2EHA), other alkyl (meth)acrylate (R 2 Less than C4 or more than C 10 The total amount of the (meth)acrylic acid alkyl ester having a chain alkyl group) in the monomer components constituting the acrylic polymer is preferably set to about 30% by weight or less (e.g., 20% by weight or less, typically, 15% by weight or less). In addition, from the viewpoint of obtaining the effect of other (meth)acrylic acid alkyl esters, the above-mentioned total amount is preferably set to about 1% by weight or more (e.g., 5% by weight or more, typically, 10% by weight or more) in the above-mentioned monomer components. As the above-mentioned other (meth)acrylic acid alkyl ester, R of the above-mentioned formula (1) can be preferably used. 2 C 1-3 (Meth)acrylic acid alkyl esters having a chain alkyl group. Specific examples thereof include methyl acrylate (MA), methyl methacrylate (MMA), ethyl acrylate (EA), etc. Among them, MA is more preferred.

[0049] The secondary monomer copolymerizable with the (meth) alkyl acrylate as the main monomer can help introduce crosslinking points into the acrylic polymer or improve the cohesive force of the acrylic polymer. As the secondary monomer, for example, one or more of the following functional group-containing monomer components can be used alone or in combination.

[0050] Carboxyl group-containing monomers: for example, ethylenically unsaturated monocarboxylic acids such as acrylic acid (AA), methacrylic acid (MAA), and crotonic acid; ethylenically unsaturated dicarboxylic acids such as maleic acid, itaconic acid, and citraconic acid, and their anhydrides (maleic anhydride, itaconic anhydride, etc.).

[0051] Hydroxyl-containing monomers: for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, etc.; unsaturated alcohols such as vinyl alcohol and allyl alcohol.

[0052] Amide group-containing monomers: for example, (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylolpropane(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide.

[0053] Amino group-containing monomers: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate.

[0054] Monomers having an epoxy group: for example, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, and allyl glycidyl ether.

[0055] Cyano-containing monomers: such as acrylonitrile and methacrylonitrile.

[0056] Ketone group-containing monomers: for example, diacetone (meth)acrylamide, diacetone (meth)acrylate, methyl vinyl ketone, ethyl vinyl ketone, allyl acetoacetate, vinyl acetoacetate.

[0057] Monomers having a nitrogen atom-containing ring: for example, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-vinylmorpholine, N-vinylcaprolactam, and N-(meth)acryloylmorpholine.

[0058] Alkoxysilyl group-containing monomers: for example, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane.

[0059] The above-mentioned monomer containing functional groups can be used alone or in combination of two or more. Among the above-mentioned monomer containing functional groups, from the aspect of appropriately realizing the introduction of crosslinking points as described above and the improvement of cohesive force, preferably carboxyl-containing monomers, hydroxyl-containing monomers, cyano-containing monomers, more preferably carboxyl-containing monomers. Among the carboxyl-containing monomers, AA and MAA are preferred.

[0060] In some preferred embodiments, AA and MAA are used in combination as the above-mentioned functional group-containing monomers. The adhesive composition of the acrylic polymer containing the monomer composition (i.e., copolymer composition) can provide a higher performance (for example, better resilience resistance) adhesive sheet. The weight ratio of AA to MAA (AA / MAA) can be set to, for example, a range of about 0.1 to 10, more preferably about 0.3 or more, further preferably 0.5 or more, and particularly preferably 1.0 or more (for example, greater than 1.0). In addition, the above-mentioned weight ratio (AA / MAA) is more preferably about 5 or less (typically 4 or less). By making AA / MAA within the above-mentioned range, there is a tendency to easily obtain the effect of improving resilience resistance, and there is also a tendency for the adhesive sheet to have excellent stability over time in the adhesive properties after production.

[0061] In addition, it is preferred that an alkoxysilyl-containing monomer is copolymerized in the acrylic polymer. The alkoxysilyl-containing monomer is typically an ethylenically unsaturated monomer having at least one (preferably two or more, for example two or three) alkoxysilyl group in one molecule, and its specific example is as described above. The above-mentioned alkoxysilyl-containing monomer can be used alone or in combination of two or more. By copolymerizing the alkoxysilyl-containing monomer, a cross-linked structure based on a condensation reaction (silanol condensation) of a silanol group can be introduced into the adhesive formed by the adhesive composition containing the acrylic polymer.

[0062] When a monomer containing a functional group is copolymerized in an acrylic polymer, the proportion of the monomer containing a functional group in all monomer components constituting the acrylic polymer is not particularly limited. Generally, from the viewpoint of taking both cohesion and adhesion into consideration in a good balance, the proportion of the monomer containing a functional group is preferably set to about 0.1% by weight or more (e.g., 0.5% by weight or more, typically, 1% by weight or more). In addition, in consideration of the adhesive effect brought about by the (meth) alkyl acrylate, it is preferably set to about 40% by weight or less (e.g., 30% by weight or less, typically, 20% by weight or less).

[0063] When the acrylic acid-based polymer is copolymerized with a carboxyl-containing monomer, it is appropriate to set the proportion of the carboxyl-containing monomer in the above-mentioned total monomer components as 15% by weight or less from the viewpoint of adhesive properties such as adhesive force, for example, it can be 10% by weight or less. In some preferred embodiments, from the viewpoint of impact resistance, the proportion of the carboxyl-containing monomer in the above-mentioned total monomer components can be 5% by weight or less, or 3% by weight or less. On the other hand, from the viewpoint of agglomeration, in some embodiments, the above-mentioned proportion can be, for example, more than 0.1% by weight or more than 0.5% by weight. In the technology disclosed herein, it can be preferably implemented in a manner of more than 1% by weight or more than 1.5% by weight in the proportion of the carboxyl-containing monomer in the above-mentioned total monomer components.

[0064] When an alkoxysilyl group-containing monomer is copolymerized in an acrylic polymer, the proportion of the alkoxysilyl group-containing monomer in the above-mentioned total monomer components is appropriately set to 0.005% by weight or more (e.g., 0.01% by weight or more), and is appropriately set to about 0.1% by weight or less (e.g., 0.03% by weight or less).

[0065] Furthermore, for the purpose of improving the cohesive force of the acrylic polymer, other copolymerization components other than the above-mentioned secondary monomers may be used. Examples of the copolymerization components include vinyl ester monomers such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene, substituted styrenes (such as α-methylstyrene) and vinyltoluene; cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate and isobornyl (meth)acrylate; aromatic ring-containing (meth)acrylates such as aryl (meth)acrylates (such as phenyl (meth)acrylate), aryloxyalkyl (meth)acrylates (such as phenoxyethyl (meth)acrylate) and arylalkyl (meth)acrylates (such as benzyl (meth)acrylate); olefin monomers such as ethylene, propylene, isoprene, butadiene and isobutylene; chlorine-containing monomers such as vinyl chloride and vinylidene chloride; isocyanate group-containing monomers such as 2-(meth)acryloyloxyethyl isocyanate; alkoxy group-containing monomers such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; vinyl ether monomers such as methyl vinyl ether and ethyl vinyl ether, etc.

[0066] As other examples of copolymerizable components other than the above-mentioned secondary monomers, monomers having multiple functional groups in one molecule can be listed. As examples of the multifunctional monomers, 1,6-hexanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, glycerol di(meth)acrylate, epoxy acrylate, polyester acrylate, urethane acrylate, divinylbenzene, butyl di(meth)acrylate, hexyl di(meth)acrylate, etc. can be listed.

[0067] The amount of copolymer components other than the above-mentioned secondary monomers can be appropriately selected according to the purpose and application, and is not particularly limited. For example, it is preferably set to be 10% by weight or less of the monomer composition of the acrylic polymer, and can be 3% by weight or less, or less than 1% by weight (for example, 0% by weight or more and less than 1% by weight).

[0068] It is appropriate to design the acrylic polymer in the technology disclosed herein so that the glass transition temperature (Tg) of the polymer is below -25°C (typically, above -75°C and below -25°C). The Tg of the acrylic polymer may be preferably below -40°C (for example, above -70°C and below -40°C), more preferably below -50°C (typically, above -70°C and below -50°C). By using an acrylic polymer with a low Tg, there is a tendency for the impact resistance to be improved. In addition, it is also preferred to set the Tg of the acrylic polymer below the above-mentioned upper limit value from the viewpoint of improving the adhesive force and the adhesion to the intermediate layer. The Tg of the acrylic polymer can be adjusted by the type and amount ratio of the monomers used in the synthesis of the polymer.

[0069] Here, the Tg of the acrylic polymer refers to the Tg obtained by the Fox equation based on the composition of the monomer components used in the synthesis of the polymer. The Fox equation is shown below, which is a relationship between the Tg of the copolymer and the glass transition temperature Tgi of the homopolymer obtained by homopolymerizing the monomers constituting the copolymer.

[0070] 1 / Tg=Σ(Wi / Tgi)

[0071] It should be noted that in the above Fox formula, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio based on weight), and Tgi represents the glass transition temperature of the homopolymer of monomer i (unit: K).

[0072] As the glass transition temperature of the homopolymer used in calculating Tg, the value described in the known documents is used. For example, for the monomers listed below, the following values ​​are used as the glass transition temperature of the homopolymer of the monomer.

[0073]

[0074]

[0075] Regarding the glass transition temperature of homopolymers of monomers other than those exemplified above, the values ​​described in “Polymer Handbook” (3rd edition, John Wiley & Sons, Inc., 1989) are adopted. When a plurality of values ​​are described in this document, the highest value is adopted.

[0076] For monomers whose glass transition temperature of homopolymers is not recorded in the above-mentioned Polymer Handbook, the value obtained by the following measurement method is used (refer to Japanese Patent Gazette No. 2007-51271). Specifically, in a reactor equipped with a thermometer, a stirrer, a nitrogen inlet pipe and a reflux condenser, 100 parts by weight of monomers, 0.2 parts by weight of azobisisobutyronitrile and 200 parts by weight of ethyl acetate as a polymerization solvent are added, and stirring is carried out for 1 hour while nitrogen is circulated. After removing oxygen in the polymerization system in this way, the temperature is raised to 63°C and allowed to react for 10 hours. Then, it is cooled to room temperature to obtain a homopolymer solution with a solid content concentration of 33% by weight. Then, the homopolymer solution is cast on a release liner and dried to prepare a test sample (sheet-shaped homopolymer) with a thickness of about 2 mm. The test sample was punched into a disc with a diameter of 7.9 mm, clamped with parallel plates, and a viscoelasticity tester (ARES, manufactured by Rheometric Co., Ltd.) was used to apply shear strain at a frequency of 1 Hz. The viscoelasticity was measured in a shear mode in a temperature range of -70 to 150°C and a heating rate of 5°C / min. The peak temperature of tanδ was taken as the Tg of the homopolymer.

[0077] The method for obtaining the acrylic polymer is not particularly limited, and various polymerization methods known as the synthesis methods of acrylic polymers, such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization, can be appropriately adopted. As a polymerization method that can be preferably adopted, emulsion polymerization can be exemplified. The method of emulsion polymerization is not particularly limited, and various monomer supply methods, polymerization conditions, and materials used, which are the same as those of conventional emulsion polymerizations known in the past, can be appropriately adopted. For example, as a monomer supply method, a one-time input method of supplying all monomer raw materials at one time, a continuous supply (drip) method, a batch supply (drip) method, etc. can be appropriately adopted. The monomer raw materials can also be dripped in the form of an aqueous emulsion. The polymerization temperature can be set, for example, to about 20°C or more (usually 40°C or more), and it is appropriate to set it to about 100°C or less (usually 80°C or less).

[0078] Utilize above-mentioned emulsion polymerization, can prepare the polymerization liquid (acrylic acid polymer emulsion) of the emulsion form that acrylic acid polymer is dispersed in water.For example, water-dispersible adhesive composition can preferably use above-mentioned polymerization liquid or the polymerization liquid obtained by suitable aftertreatment to this polymerization liquid to manufacture.Or, also can utilize the polymerization method (for example, solution polymerization, photopolymerization, bulk polymerization etc.) synthetic acrylic acid polymer except emulsion polymerization method, make this polymer dispersed in water to prepare acrylic acid polymer emulsion.Usually, by using the acrylic acid polymer emulsion designed to relatively high molecular weight, there is the tendency that easily obtains good processability.

[0079] The initiator used in the polymerization can be appropriately selected from conventionally known polymerization initiators according to the type of polymerization method. Examples thereof include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] hydrate, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), 2,2'-azobis[2-(2-imidazoline-2 -1-propane] dihydrochloride and other azo initiators; persulfate initiators such as potassium persulfate and ammonium persulfate; peroxide initiators such as benzoyl peroxide, tert-butyl hydroperoxide, hydrogen peroxide and the like; substituted ethane initiators such as phenyl substituted ethane; carbonyl initiators such as aromatic carbonyl compounds; redox initiators such as a combination of persulfate and sodium bisulfite, a combination of peroxide and sodium ascorbate; etc., but not limited to these. Such polymerization initiators can be used alone or in combination of two or more.

[0080] The amount of the polymerization initiator used is not particularly limited as long as it is a common amount, and can be selected from a range of about 0.005 parts by weight or more (preferably 0.01 parts by weight or more) and about 1 part by weight or less (preferably 0.8 parts by weight or less) relative to 100 parts by weight of the total monomer components.

[0081] During polymerization, a chain transfer agent may be used as needed (it may also be used as a molecular weight modifier or a polymerization degree modifier). Examples of the chain transfer agent include mercaptans such as dodecyl mercaptan (dodecyl mercaptan), lauryl mercaptan, glycidyl mercaptan, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl thioglycolate, and 2,3-dimercapto-1-propanol, and α-methylstyrene dimer. Such chain transfer agents may be used alone or in combination of two or more.

[0082] The amount of the chain transfer agent used can be about 0.001 parts by weight or more (typically about 0.005 parts by weight or more, for example about 0.001 parts by weight or more) relative to 100 parts by weight of the monomer component, and can also be about 5 parts by weight or less (typically about 2 parts by weight or less, for example about 1 part by weight or less). By setting the amount of the chain transfer agent used in an appropriate range, the desired polymerization rate can be obtained.

[0083] The emulsion polymerization of the monomer raw material is usually carried out in the presence of a surfactant (emulsifier). The amount of the surfactant is not particularly limited. Considering the polymerization stability and the dispersion stability of the polymerization reactant, it is appropriate to set the amount of the surfactant to 0.1 parts by weight or more relative to 100 parts by weight of the monomer raw material, preferably to 0.5 parts by weight or more, and from the viewpoint of obtaining higher stability, it can be set to 1.0 parts by weight or more, or it can be set to 1.5 parts by weight or more. In addition, the amount of the surfactant can be set to less than 10 parts by weight relative to 100 parts by weight of the monomer raw material. On the other hand, from the viewpoint of adhesive properties, it is desirable to suppress the amount of the surfactant (particularly the non-reactive surfactant). From this viewpoint, the amount of the surfactant is usually preferably set to less than 5 parts by weight, can be less than 4 parts by weight, can be less than 3 parts by weight, or can be less than 2.5 parts by weight.

[0084] As the surfactant, known anionic surfactants, nonionic surfactants, cationic surfactants, etc. can be used. Anionic or nonionic surfactants are usually preferred. Surfactants having reactive functional groups (typically free radical polymerizable functional groups) can also be used. Hereinafter, surfactants having reactive functional groups are referred to as reactive surfactants, and in contrast, common surfactants that do not have reactive functional groups are sometimes referred to as non-reactive surfactants. Surfactants can be used alone or in combination of two or more.

[0085] Examples of non-reactive anionic surfactants include alkyl sulfates such as lauryl sulfate and octadecyl sulfate; fatty acid salts; alkylbenzene sulfonates such as nonylbenzene sulfonate and dodecylbenzene sulfonate; naphthalene sulfonates such as dodecylnaphthalene sulfonate; alkyldiphenyl ether disulfonates such as dodecyldiphenyl ether disulfonates; polyoxyethylene alkyl ether sulfates such as polyoxyethylene octadecyl ether sulfate and polyoxyethylene lauryl ether sulfate; polyoxyethylene alkylphenyl ether sulfates such as polyoxyethylene lauryl phenyl ether sulfate; polyoxyethylene styrenated phenyl ether sulfates; sulfosuccinates such as lauryl sulfosuccinate and polyoxyethylene lauryl sulfosuccinate; polyoxyethylene alkyl ether phosphates; polyoxyethylene alkyl ether acetates; etc. When the anionic surfactant forms a salt, the salt may be, for example, a metal salt (preferably a monovalent metal salt) such as a sodium salt, potassium salt, calcium salt, or magnesium salt, an ammonium salt, an amine salt, or the like.

[0086] Examples of non-reactive nonionic surfactants include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether and polyoxyethylene stearyl ether; polyoxyethylene alkyl phenyl ethers such as polyoxyethylene octylphenyl ether and polyoxyethylene nonylphenyl ether; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monostearate and polyoxyethylene sorbitan monolaurate; polyoxyethylene glycerol ether fatty acid esters; polyoxyethylene-polyoxypropylene block copolymers; and the like.

[0087] As the reactive surfactant, a surfactant having a polymerizable (typically free radical polymerizable) functional group can be preferably used. For example, a reactive surfactant having a structure in which a free radical polymerizable functional group is introduced into the anionic surfactant or nonionic surfactant as described above can be used. The type of free radical polymerizable functional group is not particularly limited, and for example, it can be an alkenyl group, an acryloyl group, a methacryloyl group, a vinyl group, a vinyl ether group (vinyloxy group), an allyl ether group (allyloxy group), etc. Specific examples of alkenyl groups include propenyl and isopropenyl (CH2=C(CH3)-). The concept of propenyl mentioned here includes 1-propenyl (CH3-CH=CH-) and 2-propenyl (CH2=CH-CH2-; sometimes also referred to as allyl group).

[0088] Examples of anionic reactive surfactants include polyoxyethylene (allyloxymethyl) alkyl ether sulfates (e.g., ammonium salts), polyoxyethylene nonyl propenyl phenyl ether sulfates (e.g., ammonium salts), alkyl allyl sulfosuccinates (e.g., sodium salts), methacryloyloxy polyoxypropylene sulfate salts (e.g., sodium salts), polyoxyalkylene alkenyl ether sulfates (e.g., ammonium salts in which the terminal of the alkenyl group is an isopropenyl group), etc. When the anionic reactive surfactant forms a salt, the salt may be, for example, a metal salt such as a sodium salt, or a non-metallic salt such as an ammonium salt or an amine salt.

[0089] Examples of the nonionic reactive surfactant include polyoxyethylene nonylpropenylphenyl ether and the like.

[0090] Examples of commercially available reactive surfactants include “Aqualon HS-05”, “Aqualon HS-10”, “Aqualon HS-1025”, “Aqualon HS-20”, “Aqualon KH-10”, “Aqualon KH-1025”, “Aqualon KH-05”, “Aqualon BC-0515”, “Aqualon BC-10”, “Aqualon BC-1025”, “Aqualon BC-20”, “Aqualon BC-2020”, “Aqualon RN-20”, “Aqualon RN-30”, “Aqualon RN-50”, “Aqualon AR-10”, “Aqualon AR-20”, “Aqualon AR-1025”, “Aqualon AR-2020” manufactured by ADEKA Corporation, and “ADEKA REASOAP SE-10N”, “ADEKA "LATEMUL PD-104", "LATEMUL PD-420", "LATEMUL PD-430", "LATEMUL PD-450" manufactured by Kao Corporation, "ELEMINOL JS-20", "ELEMINOL RS-3000" manufactured by Sanyo Chemical Co., Ltd., "Antox MS-60" manufactured by Nippon Emulsifier Co., Ltd., etc.

[0091] From the viewpoint of emulsification performance and the like, an anionic reactive surfactant can be preferably used in some embodiments.

[0092] When a nonionic reactive surfactant is used, a better result can be achieved by using it in combination with other surfactants, for example, anionic reactive surfactants, anionic non-reactive surfactants, nonionic non-reactive surfactants, etc.

[0093] In the method of using a surfactant, from the viewpoint of adhesive properties, the surfactant preferably includes a reactive surfactant. In other words, at least a part of the surfactant used is preferably a reactive surfactant. The monomer raw material is emulsion polymerized in the presence of a reactive surfactant, so that the above-mentioned reactive surfactant reacts and can enter the acrylic polymer. By allowing the reactive surfactant to enter the acrylic polymer, the free surfactant becomes less. The movement of the reactive surfactant entering the acrylic polymer in the adhesive layer is restricted, so it is not easy to seep out to the surface of the adhesive layer. Therefore, the use of a reactive surfactant for polymerization is advantageous for taking into account both polymerization stability and the adhesive properties of the adhesive layer obtained by the adhesive composition containing the acrylic polymer after polymerization. From the viewpoint of achieving more excellent adhesive properties, the proportion of the reactive surfactant in the total weight of the surfactant used during emulsion polymerization can be set to 50% by weight or more, more preferably 70% by weight or more, for example, it is preferred to use only a reactive surfactant as a surfactant. It should be noted that in this specification, the reactive surfactant is included in the state after the reactive functional group (such as a free radical polymerizable functional group) reacts. The reactive surfactant in the art disclosed herein is typically contained in the water-dispersible PSA composition or the PSA layer in a form in which at least a portion of the reactive surfactant is incorporated into the acrylic polymer as described above.

[0094] The weight average molecular weight (Mw) of the acrylic polymer is not particularly limited, and may be, for example, 10×10 4 ~500×10 4 Here, the Mw of the acrylic polymer refers to the Mw of the toluene soluble component (sol component) of the acrylic polymer. The Mw of the acrylic polymer refers to the value calculated based on standard polystyrene based on GPC (gel permeation chromatography). From the viewpoint of improving the adhesive properties, the Mw of the acrylic polymer is preferably 150×10 4 Less than, more preferably 100×10 4 From the viewpoint of aggregation, the Mw of the acrylic polymer may be preferably 20×10 4 More preferably 30×10 4 Above (e.g. 40×10 4 As the Mw increases, good processability tends to be more easily obtained.

[0095] (Tackifying resin)

[0096] In some preferred embodiments, the adhesive layer includes a tackifying resin. Thus, it is easy to obtain an adhesive sheet showing excellent adhesive properties (e.g., adhesive strength, resilience resistance). As the tackifying resin, for example, rosin-based tackifying resins (including rosin derivative tackifying resins), petroleum-based tackifying resins, terpene-based tackifying resins, phenol-based tackifying resins, ketone-based tackifying resins, etc. can be listed. These can be used alone or in combination of two or more.

[0097] Examples of the rosin-based tackifying resin include, in addition to rosins such as gum rosin, wood rosin, and tall oil rosin, stabilized rosin (e.g., stabilized rosin obtained by disproportionation or hydrogenation of the above rosin), polymerized rosin (e.g., a polymer of the above rosin, typically a dimer), and modified rosin (e.g., unsaturated acid-modified rosin obtained by modification with an unsaturated acid such as maleic acid, fumaric acid, or (meth)acrylic acid).

[0098] Examples of the rosin derivative tackifying resin include esters of the rosin-based resins (e.g., rosin esters such as stabilized rosin esters and polymerized rosin esters), phenol-modified rosin-based resins (phenol-modified rosin), and esters thereof (phenol-modified rosin esters).

[0099] Examples of the petroleum-based tackifying resin include aliphatic petroleum resins, aromatic petroleum resins, copolymerized petroleum resins, alicyclic petroleum resins, and hydrogenated products thereof.

[0100] Examples of the terpene-based tackifier resin include α-pinene resin, β-pinene resin, aromatic modified terpene-based resin, and terpene-phenol-based resin.

[0101] Examples of the ketone-based tackifier resin include ketone-based resins formed by condensation of ketones (eg, aliphatic ketones such as methyl ethyl ketone, methyl isobutyl ketone, and acetophenone; alicyclic ketones such as cyclohexanone and methylcyclohexanone) and formaldehyde.

[0102] Examples of tackifying resins that can be preferably used in the technology disclosed herein include rosin-based tackifying resins and terpene-based tackifying resins. Suitable examples of rosin-based tackifying resins include stabilized rosin esters and polymerized rosin esters. In addition, suitable examples of terpene-based tackifying resins include terpene phenolic resins.

[0103] The softening point of the tackifier resin used is not particularly limited. From the viewpoint of improving cohesive force, the softening point of the tackifier resin may be, for example, 80°C or higher, preferably 90°C or higher, 100°C or higher, 120°C or higher, or 130°C or higher.

[0104] Although not particularly limited, in some embodiments, the tackifier resin may include a high softening point tackifier resin having a softening point of 140°C or more. The softening point of the high softening point tackifier resin is preferably above 145°C, for example, it may be above 150°C, above 155°C, above 160°C, or above 165°C. By using the high softening point tackifier resin, adhesion and aggregation can be well balanced. The upper limit of the softening point of the tackifier resin is not particularly limited. From the viewpoint of compatibility, low temperature characteristics, etc., it is generally appropriate to be below 200°C, preferably below 180°C, and may be below 175°C.

[0105] It should be noted that the softening point of the tackifying resin mentioned here is defined as the value measured based on the softening point test method (ring and ball method) specified in JIS K5902 and JIS K2207. Specifically, the sample is melted rapidly at the lowest possible temperature, and is filled in a ring placed on a flat metal plate while being careful not to generate bubbles. After cooling, the portion protruding from the plane containing the upper end of the ring is cut off with a slightly heated knife. Next, a support (ring stand) is placed in a glass container (heating bath) with a diameter of more than 85 mm and a height of more than 127 mm, and glycerin is injected until the depth is more than 90 mm. Next, a steel ball (diameter 9.5 mm, weight 3.5 g) is immersed in glycerin in a manner that the ring filled with the sample does not contact each other, and the temperature of the glycerin is maintained at 20°C ± 5°C for 15 minutes. Next, the steel ball is placed in the center of the surface of the sample in the ring and is placed in a fixed position on the support. Next, keep the distance from the upper end of the ring to the glycerin surface at 50 mm, place a thermometer so that the center of the mercury ball of the thermometer is at the same height as the center of the ring, and heat the container. The flame of the Bunsen burner used in heating is located between the center and the edge of the bottom of the container to make the heating uniform. It should be noted that the increase rate of the bath temperature from the start of heating to reaching 40°C must be 5.0±0.5°C per minute. Read the temperature when the sample gradually softens and flows down from the ring and finally contacts the bottom plate, and use it as the softening point. The softening point is measured at more than 2 times at the same time and the average value is adopted.

[0106] In the mode in which the adhesive layer is formed by a water-dispersible adhesive composition, as a tackifying resin, preferably a water-dispersible tackifying resin (also referred to as a tackifying resin emulsion) is used. In this mode, the water-dispersible adhesive composition includes the tackifying resin in the form of an emulsion in which the tackifying resin is dispersed in water. For example, by mixing an aqueous emulsion of an acrylic polymer with an emulsion of the above-mentioned tackifying resin, it is possible to easily prepare an adhesive composition containing these components in a desired ratio. As a tackifying resin emulsion, it is preferred to use a tackifying resin emulsion that is at least substantially free of aromatic hydrocarbon solvents (more preferably substantially free of aromatic hydrocarbon solvents and other organic solvents).

[0107] Such an emulsion of a tackifying resin can be prepared using a surfactant (emulsifier) ​​as needed. As a surfactant that can be used in the preparation of the above-mentioned tackifying resin emulsion, one or more surfactants can be appropriately selected from the same surfactants as those that can be used in the preparation of the acrylic polymer emulsion. An anionic surfactant or a nonionic surfactant is usually preferably used. It should be noted that the surfactant used in the preparation of the acrylic polymer emulsion may be the same as or different from the surfactant used in the preparation of the tackifying resin emulsion. For example, it is preferred to use an anionic surfactant in the preparation of any emulsion; a nonionic surfactant; an anionic surfactant on one side and a nonionic surfactant on the other side. The amount of the surfactant is not particularly limited as long as it is an amount that can prepare the tackifying resin in the form of an emulsion. For example, it can be set to about 0.2 parts by weight or more (preferably 0.5 parts by weight or more) relative to 100 parts by weight of the tackifying resin (solid content basis), and it can be set to about 10 parts by weight or less (preferably 5 parts by weight or less).

[0108] For the consumption (solid content basis) of tackifying resin, from the viewpoint of playing its use effect well, it is appropriate to be set to more than 1 weight portion relative to 100 weight portions of base polymer (such as acrylic polymer), preferably more than 3 weight portions (such as more than 5 weight portions), more preferably more than 12 weight portions, more preferably more than 16 weight portions. According to technology disclosed herein, the mode of tackifying resin comprising more than 22 weight portions (such as more than 25 weight portions) relative to 100 weight portions of base polymer can also realize good adhesive properties. In addition, from the viewpoint of cohesion etc., it is appropriate to set the consumption of tackifying resin to less than 90 weight portions relative to 100 weight portions of base polymer, preferably less than 70 weight portions, more preferably less than 55 weight portions, more preferably less than 50 weight portions (such as less than 45 weight portions, typically less than 40 weight portions).

[0109] In the case where the adhesive layer disclosed herein includes a high softening point tackifying resin, from the viewpoint of cohesion, etc., only the high softening point tackifying resin can be used as the tackifying resin. In addition, from the viewpoint of obtaining a balance with various adhesive properties, in some methods, a high softening point tackifying resin and a tackifying resin with a lower softening point (for example, a tackifying resin with a softening point below 120°C or below 110°C) can be used in combination. In the described method, the proportion of the high softening point tackifying resin in the overall tackifying resin used can be, for example, more than 20% by weight, more than 40% by weight, or more than 60% by weight. The proportion of the above-mentioned high softening point tackifying resin can be, for example, less than 90% by weight, less than 80% by weight, or less than 70% by weight. It is advantageous to limit the amount of the high softening point tackifying resin to less than a specified amount from the viewpoint of impact resistance.

[0110] (Polyacrylic acid)

[0111] In some embodiments, the PSA layer may contain polyacrylic acid. For example, by making the acrylic acid-based water-dispersible PSA composition contain an appropriate amount of polyacrylic acid having an appropriate number average molecular weight, the water resistance of the PSA layer formed from the water-dispersible PSA composition can be improved.

[0112] The molecular weight of the polyacrylic acid is not particularly limited. For example, polyacrylic acid having a number average molecular weight (Mn) of 2000 or more and 550×10 4 In some preferred embodiments, the Mn of the polyacrylic acid may be greater than 3000 and less than 500×10 4 Less than, or more than 5000 and 500×10 4 As the Mn of polyacrylic acid increases, the effect of improving water resistance tends to be more easily exerted. From this viewpoint, the Mn of polyacrylic acid is preferably 1×10 4 More than (e.g. 5×10 4 More preferably, 10×10 4 More preferably, 15×10 4 Above, it can also be 20×10 4 On the other hand, if the Mn of polyacrylic acid is too high, the viscosity of the adhesive composition (specifically, the water-dispersible adhesive composition) increases sharply due to the addition of the polyacrylic acid, which makes it easy to cause disadvantages such as reduced coating properties, and sometimes it is difficult to contain an amount of polyacrylic acid suitable for improving water resistance. From this point of view, the Mn of polyacrylic acid is preferably 400×10 4 Below, more preferably 300×10 4 Below, more preferably 200×10 4 In one embodiment of the technology disclosed herein, the Mn of the polyacrylic acid may be 150×10 4Below, can be 100×10 4 Below, can also be 75×10 4 Below, can be 50×10 4 Below, can also be 35×10 4 the following.

[0113] Here, in this specification, the number average molecular weight (Mn) means a value calculated in terms of standard polyethylene glycol / polyethylene oxide obtained by GPC measurement.

[0114] In the method of using polyacrylic acid, the amount of the polyacrylic acid is set in a manner that suitably exerts its addition effect. In some methods, polyacrylic acid is used in a content of more than 0.3 parts by weight and less than 7 parts by weight relative to 100 parts by weight of the base polymer. Relative to 100 parts by weight of the base polymer, the content of polyacrylic acid is more preferably more than 0.4 parts by weight, and more preferably more than 0.5 parts by weight. In some methods, relative to 100 parts by weight of the base polymer, the content of polyacrylic acid can be more than 1 part by weight, or more than 1.5 parts by weight. In addition, from the viewpoint of coating properties and forming a good adhesive layer in surface state, relative to 100 parts by weight of the base polymer, the content of polyacrylic acid is more preferably less than 6 parts by weight, and more preferably less than 5 parts by weight (for example, less than 4.5 parts by weight). In one method of the technology disclosed herein, relative to 100 parts by weight of the base polymer, the content of polyacrylic acid can be less than 4.25 parts by weight, or less than 4 parts by weight.

[0115] (Crosslinking agent)

[0116] The adhesive composition for forming the adhesive layer may contain a crosslinking agent as an optional component. The adhesive layer in the technology disclosed herein may contain the crosslinking agent in a form after a crosslinking reaction, a form before a crosslinking reaction, a form partially subjected to a crosslinking reaction, an intermediate or composite form thereof, etc. The crosslinking agent is typically contained in the adhesive layer mainly in a form after a crosslinking reaction.

[0117] The type of crosslinking agent is not particularly limited. For example, it can be appropriately selected from isocyanate crosslinking agents, epoxy crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, melamine crosslinking agents, peroxide crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, hydrazine crosslinking agents, amine crosslinking agents, etc. As the crosslinking agent used here, both oil-soluble and water-soluble crosslinking agents can be used. The crosslinking agent can be used alone or in combination of two or more. The amount of the crosslinking agent is not particularly limited. For example, it is appropriate to set it to about 10 parts by weight or less (for example, about 0.005 to 10 parts by weight) relative to 100 parts by weight of the base polymer (for example, an acrylic polymer), preferably about 5 parts by weight or less (0.01 to 5 parts by weight). The technology disclosed herein can preferably be implemented in a manner using an adhesive composition that does not contain a crosslinking agent.

[0118] (Other added ingredients)

[0119] In addition, from the viewpoint of the light peelability of the self-peeling liner, the adhesive layer can include a silicon compound (typically a silane coupling agent). As the silicon compound, one or more of an alkyl alkoxy silane compound, a vinyl-containing silane compound, an epoxy-containing silane compound, a styrene-containing silane compound, a (methyl) acryl-containing silane compound, an amino-containing silane compound, a urea-containing silane compound, a mercapto-containing silane compound, an isocyanate-containing silane compound, a silyl-containing sulfide, etc. can be used. Among them, an alkyl alkoxy silane compound is preferred. It is appropriate that the molecular weight of the silicon compound is about 100 or more (for example, more than 200), and can also be about 500 or less (for example, less than 350).

[0120] As alkyl alkoxysilane compound, alkyl trialkoxy silane, dialkyl dialkoxy silane, trialkyl monoalkoxy silane, tetraalkoxy silane, phenyl alkoxy silane can all be used.It should be noted that the above-mentioned alkyl includes chain and ring.As the specific example of the above-mentioned compound, methyl trimethoxy silane, ethyl trimethoxy silane, n-propyl trimethoxy silane, n-butyl trimethoxy silane, isobutyl trimethoxy silane, n-hexyl trimethoxy silane, n-octyl trimethoxy silane, n-decyl trimethoxy silane, hexadecyl trimethoxy silane, methyl triethoxy silane, dimethoxy dimethyl silane, diethoxy dimethyl silane, cyclohexyl methyl dimethoxy silane, methoxy trimethyl silane, octadecyl dimethyl methoxy silane, phenyl trimethoxy silane, phenyl triethoxy silane, dimethoxy diphenyl silane, diphenyl ethoxy methyl silane, dimethoxy methyl phenyl silane etc. can be listed.Wherein, preferred alkyl trialkoxy silane.

[0121] The content of the silicon compound is preferably 0.005 parts by weight or more (e.g., 0.01 parts by weight or more, typically 0.03 parts by weight or more) relative to 100 parts by weight of the base polymer (e.g., acrylic polymer) from the viewpoint of fully expressing the effect of addition. In addition, from the viewpoint of storage stability, the content of the silicon compound is preferably less than 1.0 parts by weight (e.g., 0.5 parts by weight or less, typically 0.3 parts by weight or less) relative to 100 parts by weight of the base polymer.

[0122] The adhesive composition disclosed herein may contain an acid or alkali (ammonia water, etc.) used for the purpose of pH adjustment, etc. as required. As other arbitrary components that can be mixed in the adhesive composition disclosed herein, viscosity modifiers, leveling agents, crosslinking aids, release modifiers, plasticizers, softeners, fillers, colorants (pigments, dyes, etc.), antistatic agents, anti-aging agents, ultraviolet absorbers, antioxidants, light stabilizers, preservatives, etc. can be exemplified. For such various additives, conventionally known additives can be used, but since they are not the characteristics of the present invention, detailed descriptions are omitted.

[0123] (Adhesive composition)

[0124] The adhesive layer disclosed herein (layer formed by adhesive) can be an adhesive layer formed by a water-based adhesive composition, a solvent-based adhesive composition, a hot melt adhesive composition, or an active energy ray-curable adhesive composition cured by irradiating active energy rays such as ultraviolet rays and electron beams. A water-based adhesive composition refers to an adhesive composition in the form of an adhesive (adhesive layer forming component) contained in a medium (aqueous medium) with water as the main component, typically including substances such as a water-dispersible adhesive composition (a composition in the form of at least a portion of the adhesive dispersed in an aqueous medium). Here, the aqueous medium refers to water or a mixed solvent or dispersion medium (aqueous solvent or aqueous dispersion medium) with water as the main component. In addition, a solvent-based adhesive composition refers to an adhesive composition in the form of an adhesive contained in an organic solvent. As the organic solvent contained in the solvent-based adhesive composition, one or more of the organic solvents (toluene, ethyl acetate, etc.) that can be used in the above-mentioned solution polymerization can be used without particular limitation. The technology disclosed herein can be preferably implemented in a form of an adhesive layer formed of a water-dispersible (typically water-based emulsion) adhesive composition in which an adhesive component is dispersed in an aqueous medium. For example, in an acrylic emulsion adhesive composition containing a water-dispersible acrylic polymer, the water-dispersible acrylic polymer is usually designed to have a high molecular weight, and there is a tendency to easily obtain good processability.

[0125] (Formation of Adhesive Layer)

[0126] The adhesive layer in the technology disclosed herein can be appropriately formed by imparting the above-mentioned adhesive composition to a specified surface and drying or curing it. When imparting (typically coating) the adhesive composition, a conventional coating machine (for example, a gravure roll coater, a reverse roll coater, a lick coater, a dip roll coater, a rod coater, a knife coater, a spray coater, etc.) can be used.

[0127] (Thickness of adhesive layer)

[0128] The thickness of the adhesive layer can be set within the range of 60 μm or less of the total thickness of the double-sided adhesive sheet and 10% to 60% of the thickness ratio of the intermediate layer. In addition, the first adhesive layer and the second adhesive layer can be the same thickness or different thicknesses from each other. It is appropriate that the thickness of the first adhesive layer and the second adhesive layer are each independently usually set to about 2 μm or more. From the viewpoint of adhesive properties such as impact resistance, adhesive force, and resilience resistance, it is preferably about 5 μm or more, more preferably 8 μm or more, and more preferably 10 μm or more, and can be 15 μm or more (for example, 18 μm or more). In addition, the thickness of the first adhesive layer and the second adhesive layer is each independently usually about 27 μm or less, and it is appropriate to set it to 25 μm or less, preferably about 20 μm or less, more preferably 16 μm or less, more preferably 14 μm or less, and particularly preferably 12 μm or less. The adhesive layer with limited thickness can cope well with the requirements of thinning and lightweighting.

[0129] <Middle Layer>

[0130] The double-sided adhesive sheet disclosed herein has an intermediate layer with a Young's modulus in the range of 1.5 to 1500 MPa. By using an intermediate layer having the above-mentioned Young's modulus, in a thin double-sided adhesive sheet with a total thickness of less than 60 μm, it is possible to preferably take into account both processability and impact resistance. The Young's modulus of the intermediate layer may be less than 1000 MPa, less than 500 MPa, less than 300 MPa, less than 100 MPa (e.g., less than 95 MPa), or less than 50 MPa. For the impact resistance that has become a subject in the technology disclosed herein, a relatively high correlation is shown with the Young's modulus of the intermediate layer in viscoelastic properties and mechanical properties. By making the Young's modulus of the intermediate layer less than the above-mentioned upper limit, there is a tendency for the impact resistance to be improved. In addition, there is a tendency for the anchoring force of the adhesive layer to also become higher. In some ways, the Young's modulus of the middle layer is less than 100MPa, preferably less than 50MPa, more preferably less than 30MPa, further preferably less than 25MPa, less than 20MPa, less than 15MPa, less than 10MPa, or less than 5MPa (for example, less than 5MPa). In addition, from the viewpoint of processability, the Young's modulus of the middle layer can be more than 3MPa, more than 8MPa, more than 12MPa, or more than 15MPa. In some ways, the Young's modulus of the middle layer is more than 30MPa, more than 50MPa, more than 75MPa, more than 150MPa, more than 400MPa, or more than 800MPa. The Young's modulus of the middle layer is specifically measured by the method described in the embodiments described later.

[0131] In addition, although not particularly limited, in some embodiments, the storage modulus of the intermediate layer at a frequency of 160 Hz (160 Hz storage modulus) is 7.0×10 6 ~5.0×10 9 Pa. It is believed that the frequency of 160 Hz corresponds to the speed range during punching. There is a tendency that the higher the storage modulus at 160 Hz, the easier it is to obtain good processability (specifically, punching processability). From this point of view, the storage modulus at 160 Hz is 1.8×10 7 The above is appropriate, preferably 5.0×10 7 Pa or more, more preferably 8.0×10 7 Pa or more, can be 1.0×10 8 Pa or more, or 3.0×10 8 Pa or more. In addition, the upper limit of the storage modulus at 160 Hz may be, for example, 3.0×10 9 Pa or less, can be 1.0×10 9 Pa or less, can be 5.0×108 Pa or less, can be 1.0×10 8 Pa or less, can be 5.0×10 7 Pa or less, or 1.0×10 7 Below Pa.

[0132] In addition, although not particularly limited, in some embodiments, the storage modulus (10 3 ~10 4 Hz storage modulus) is 3.7×10 9 Pa or less. It is believed that the above frequency range corresponds to the velocity range of the impact (for example, the impact in the impact resistance test described later, such as the drop impact). 3 ~10 4 The higher the storage modulus at Hz, the easier it is to obtain good impact resistance. 3 ~10 4 The storage modulus at Hz is preferably 1.0×10 9 Pa or less, more preferably 5.0×10 8 Pa or less, more preferably 3.0×10 8 Pa or less, can be 1.0×10 8 Pa or less, or 1.0×10 7 Pa or less. In addition, the above 10 3 ~10 4 The lower limit of the storage modulus at Hz can be, for example, 1.0×10 6 Pa or more, can be 5.0×10 6 Pa or more, can be 1.0×10 7 Pa or more, can be 5.0×10 7 Pa or more, can be 1.0×10 8 Pa or more, can be 5.0×10 8 Pa or more, or 1.0×10 9 Pa or above.

[0133] The above frequencies (160Hz and 10 3 ~10 4 The storage modulus at 250 Hz) is the storage modulus at a reference temperature of 25° C., and is specifically measured by the method described in the Examples described below.

[0134] In addition, the intermediate layer disclosed herein is formed by water-dispersible material. In this specification, water-dispersible material refers to the material in which at least a part of the intermediate layer forming material such as polymer, filler is dispersed in the form of aqueous medium. Aqueous medium refers to water or a mixed solvent or dispersion medium (aqueous solvent or aqueous dispersion medium) with water as the main component. As a typical example of water-dispersible material, aqueous dispersions of intermediate layer forming materials such as polymer can be listed. By using water-dispersible material as the intermediate layer forming material, it is possible to prevent or suppress the migration of components that may be produced between the adhesive layer. The above-mentioned interlayer component migration means that it is not easy to produce the characteristic change of the adhesive sheet caused by the migration of this component. In such a thin adhesive sheet disclosed herein, even a small amount of component migration is also easy to become larger on the impact of each characteristic such as bonding characteristics, and therefore, it is important to prevent or suppress the migration of interlayer components in practical application.

[0135] For the purpose of dispersibility and stability of the material, the above-mentioned water-dispersible material may contain an emulsifier (surfactant) or may not contain an emulsifier substantially. Here, the water-dispersible material substantially does not contain an emulsifier means that an emulsifier is not used intentionally, for example, the content of the emulsifier in the water-dispersible material is less than 0.1% by weight (for example, less than 0.01% by weight or less than 0.001% by weight) based on the solid content. For example, among the water-dispersible resins such as the water-dispersible polyurethane resin described later, the so-called self-emulsifying and soap-free materials are typical examples of water-dispersible materials that do not contain an emulsifier.

[0136] As the material constituting the middle layer, various resin materials capable of achieving the above-mentioned Young's modulus can be used. For example, an middle layer formed by a resin layer (resin film) can be preferably used. As the resin film used for the middle layer, a non-foamed resin film and a rubber-like film are preferred. From the viewpoint of processability, a non-foamed resin film is more preferred. It should be noted that in this specification, "resin film" is a substantially non-porous film, which is a concept different from the so-called non-woven fabric and woven fabric (that is, the concept of non-woven fabric and woven fabric is not included). In addition, a non-foamed resin film refers to a resin film that has not been intentionally treated to form a foamed body. Specifically, the non-foamed resin film can be a resin film having a foaming ratio less than 1.1 times (for example, less than 1.05 times, typically less than 1.01 times).

[0137] As examples of resin materials constituting the intermediate layer, polyurethane resins; polyolefin resins; acrylic resins such as acrylic copolymers; vinyl chloride resins (PVC) such as soft polyvinyl chloride; silicones such as silicone rubber; blends and hybrids (also called composites) of the above resins; etc. As hybrids of the above resins, for example, urethane-acrylic hybrids and silicone-urethane hybrids can be exemplified. In addition, the material constituting the intermediate layer can be rubber (usually including materials referred to as rubber and thermoplastic elastomers). By selecting and using an appropriate one or more of the above materials, an intermediate layer with a target Young's modulus can be obtained. In some embodiments, as the resin material contained in the intermediate layer, polyurethane resins, polyolefin resins, rubbers, acrylic resins, and blends thereof (such as acrylic urethane resins) can be used. By selecting appropriate types from these materials, it is possible to preferably take into account both processability and impact resistance. Among them, polyurethane resins and acrylic urethane resins are preferred.

[0138] In some preferred embodiments, the middle layer is formed by comprising a polyurethane resin (specifically, a water-dispersible polyurethane resin). By selecting one or more appropriate polyurethane resins from the polyurethane resins and using them, an middle layer with a target Young's modulus can be preferably obtained. In addition, according to the middle layer comprising the polyurethane resin, for example, in the mode of laminating an acrylic adhesive layer, it is easy to obtain good anchoring properties, and anchoring damage is not easy to occur when impacted, and excellent impact resistance is easy to obtain. Here, the polyurethane resin refers to a polymer compound synthesized by making a polyol (such as a diol) and a polyisocyanate (such as a diisocyanate) react with a suitable ratio. As a polyol, there is no particular limitation, and one or more appropriate polyols can be selected from various diols, polyester polyols, polyether polyols, carbonate diols, etc., and used. As a polyisocyanate, there is no particular limitation, and one or more appropriate polyisocyanates can be selected from aromatic, aliphatic, alicyclic diisocyanates, polymers of these diisocyanates (such as dimers, trimers), etc., and used. In the synthesis of polyurethane resin, the NCO / OH ratio is appropriately set in a manner to obtain the desired mechanical properties. In addition to polyols and polyisocyanates, other copolymer components (such as carboxylic acids, etc.) can also be introduced into the polyurethane resin. It is appropriate that the proportion of the above-mentioned other copolymer components is less than about 10% by weight (for example, 0 to 3% by weight) in the polyurethane resin. As the polyurethane resin, ether polyurethane, ester polyurethane, and carbonate polyurethane can all be used, among which ester polyurethane is preferred.

[0139] In some embodiments, the polyurethane resin contained in the middle layer can be an acrylic carbamate resin. As acrylic carbamate resins, for example, there can be listed reaction products of acrylic polymers (specifically, polyol-type acrylic copolymers) having two or more hydroxyl groups and isocyanate compounds, and copolymers of carbamate prepolymers having ethylenically unsaturated groups at both ends and (meth) alkyl acrylates. The above-mentioned acrylic carbamate resins can also be carbamate-acrylic hybrids. As the above-mentioned carbamate-acrylic hybrids, for example, there can be listed water-dispersible carbamate-acrylic hybrids obtained by using a carbamate prepolymer in a carbamate prepolymer aqueous dispersion as a seed and performing seed polymerization on a (meth) acrylic monomer.

[0140] In other embodiments, in the middle layer, as a polyurethane resin, a resin containing a carbamate (meth) acrylate polymer is formed. As the carbamate (meth) acrylate polymer disclosed herein, a polymer containing a structural unit from a carbamate (meth) acrylate can be used. Here, carbamate (meth) acrylate refers to a compound having a carbamate bond and a (meth) acryloyl group in one molecule, and the compound can be used without particular limitation. One type of carbamate (meth) acrylate can be used alone or two or more types can be used in combination. The carbamate (meth) acrylate polymer can be synthesized by a known method. In addition, various commercially available carbamate (meth) acrylates can be used.

[0141] The polyurethane resin can be formed into a film by a known method, or a commercial product can be used. Examples of the commercial product include "UCOAT DA-100" manufactured by Sanyo Chemical Industry Co., Ltd., "ADEKA BONTIGHTER HUX" series manufactured by ADEKA Co., Ltd., and "SUPERFLEX" series manufactured by Daiichi Kogyo Seiyaku Co., Ltd.

[0142] In other embodiments, the intermediate layer may be formed by including a polyolefin resin (specifically, a water-dispersible polyolefin resin). By selecting one or more appropriate polyolefin resins from the polyolefin resins and using them, an intermediate layer with a target Young's modulus can be obtained. The polyolefin resin may be, for example, a homopolymer of an α-olefin, a copolymer of two or more α-olefins, a copolymer of one or more α-olefins and other vinyl monomers, and the like. As specific examples, ethylene-propylene copolymers such as polyethylene (PE), polypropylene (PP), poly-1-butene, poly-4-methyl-1-pentene, ethylene-propylene rubber (EPR), ethylene-propylene-butene copolymers, ethylene-butene copolymers, ethylene-vinyl alcohol copolymers, ethylene-ethyl acrylate copolymers, and the like can be cited. Both low-density (LD) polyolefins and high-density (HD) polyolefins can be used. The polyolefin resin may be an ionomer. As examples of commercially available products of the above-mentioned polyolefin resins, the trade name "CHEMIPEARL" series manufactured by Mitsui Chemicals, Inc. can be cited.

[0143] In other embodiments, the middle layer can be formed by including rubber (specifically, water-dispersible rubber. Also called latex). By selecting one or more types of rubber for use, an middle layer having a target Young's modulus can be obtained. Examples of rubbers include styrene-butadiene copolymers, styrene-isoprene copolymers, styrene-ethylene-butylene copolymers, styrene-ethylene-propylene copolymers, styrene-butadiene-styrene copolymers, styrene-isoprene-styrene copolymers, and their modified products, and other styrene-based copolymers (typically styrene-based elastomers). Examples of commercially available products of the above-mentioned rubbers include the "Nipol" series manufactured by ZEON CORPORATION., and the like.

[0144] In other embodiments, the middle layer may be formed by including an acrylic resin (specifically, a water-dispersible acrylic resin). The acrylic polymer that becomes the acrylic resin may be a homopolymer or a copolymer (a random copolymer, a block copolymer, a graft copolymer, etc.). The acrylic resin also includes a resin called acrylic rubber. The acrylic resin is preferably used in the form of a blend or a hybrid with a polyurethane resin. As the acrylic resin, an acrylic resin having properties suitable as an intermediate layer material may be used without particular limitation, for example, an acrylic resin synthesized by a known or customary method may be used, or a commercially available product may be used.

[0145] In other embodiments, the intermediate layer may be formed by including silicone. The above-mentioned silicone includes silicone rubber. The silicone is preferably used in the form of a blend or hybrid with a polyurethane resin. As the silicone, silicone synthesized by a known method may be used, or a commercially available product may be used. For example, as an example of a commercially available silicone-urethane hybrid resin, the trade name "CHALINE RU-911" manufactured by Nissin Chemical Industry Co., Ltd. may be cited.

[0146] In some embodiments, the intermediate layer may include filler particles in addition to the various resins mentioned above. By using filler particles, the Young's modulus of the intermediate layer is improved, and it is easy to obtain better processability. As filler particles, both organic materials and inorganic materials can be used, for example, metal filler particles; metal oxide fillers such as silica; metal hydroxide filler particles; carbonates such as calcium carbonate; and other inorganic materials are preferably used. Filler particles can be used alone or in combination of two or more. From the perspective of dispersibility with the resin, the filler particles are preferably added in the form of an aqueous dispersion. The particle size of the filler particles is not particularly limited, and filler particles of appropriate size can be used according to the thickness and dispersibility of the intermediate layer to which the filler particles are added.

[0147] In the method in which the middle layer includes filler particles, the content of the filler particles is not particularly limited. From the viewpoint of effectively exerting the addition effect of the filler particles, the compounding amount of the filler particles is, for example, 1 part by weight or more relative to 100 parts by weight of the resin contained in the middle layer, and it is appropriate to be 10 parts by weight or more, and it can be 20 parts by weight or more, or it can be 30 parts by weight or more. The upper limit of the compounding amount of the filler particles is, for example, less than 100 parts by weight relative to 100 parts by weight of the above-mentioned resin, and it is appropriate to set it to about 70 parts by weight or less. In other methods, the content of the filler particles in the middle layer is, for example, less than 30 parts by weight relative to 100 parts by weight of the resin contained in the middle layer, and it can be less than 10 parts by weight or less than 1 part by weight. The middle layer disclosed herein may be substantially free of filler particles.

[0148] The intermediate layer may be mixed with various additives such as leveling agents, thickeners, anti-aging agents, antioxidants, ultraviolet absorbers, antistatic agents, lubricants, plasticizers, colorants (pigments, dyes, etc., such as carbon black, etc.), preservatives, etc. as needed. The surface of the intermediate layer (especially the surface on the side where the adhesive layer is provided) may be subjected to known or customary surface treatments such as corona discharge treatment, plasma treatment, and application of a primer. Such surface treatments may be, for example, treatments for improving the anchoring properties of the substrate of the adhesive layer. It should be noted that, in the case where the intermediate layer contains a polyurethane resin, good anchoring properties may be obtained even without the above-mentioned surface treatments, depending on the surface energy thereof.

[0149] The intermediate layer may be a single layer structure, or a multilayer structure of two layers, three layers or more. For example, the intermediate layer may be substantially composed of a resin layer containing the above resin. The intermediate layer may also contain an auxiliary layer in addition to the above resin layer.

[0150] The method for manufacturing the intermediate layer is not particularly limited as long as it appropriately adopts a conventionally known film forming method. When a resin film is used as the intermediate layer, for example, conventionally known general film forming methods such as extrusion molding, inflation molding, T-die casting molding, and calendering roll molding can be appropriately adopted. In addition, the intermediate layer can be appropriately formed by coating the intermediate layer forming material (e.g., an aqueous dispersion of a resin) on a specified surface (e.g., a peelable surface) and curing it by drying or the like.

[0151] The thickness of the intermediate layer is set so that the thickness ratio of the intermediate layer relative to the total thickness of the double-sided adhesive sheet is within the range of 10% to 60%. Thus, in a thin double-sided adhesive sheet, both processability and impact resistance can be preferably taken into account. The thickness ratio of the intermediate layer can be 55% or less, or 50% or less. In some preferred embodiments, from the perspective of impact resistance, the thickness ratio of the intermediate layer is less than 50%, more preferably 45% or less, further preferably 40% or less, particularly preferably 35% or less, and can be 30% or less. By setting the thickness ratio of the intermediate layer to be relatively low, there is a tendency that the adhesive properties such as adhesion and resilience resistance are also improved. In other preferred embodiments, the thickness ratio of the intermediate layer can be 25% or less, or 20% or less (for example, 15% or less). In a structure with a small thickness ratio of the intermediate layer like this, the effect brought about by the technology disclosed herein can be appropriately exerted. In addition, in some preferred embodiments, from the viewpoints of productivity, handling, etc., the lower limit of the thickness ratio of the intermediate layer may be 15% or more, 20% or more, 25% or more (e.g., more than 25%), 26% or more, 27% or more, or 30% or more (e.g., more than 30%). In other embodiments, the thickness ratio of the intermediate layer may be 35% or more, 40% or more, or 45% or more.

[0152] Specifically, the thickness of the intermediate layer is, for example, about 1 μm or more, usually 3 μm or more, preferably 5 μm or more, more preferably 7 μm or more, and further preferably 9 μm or more. According to the technology disclosed herein, the thickness of the intermediate layer is set to a predetermined value or more, and good processability, handling, etc. can be obtained, and excellent impact resistance can be achieved. From this point of view, the thickness of the intermediate layer can be 10 μm or more, 15 μm or more, 18 μm or more, or 22 μm or more. The upper limit of the thickness of the intermediate layer is about 36 μm or less, preferably 30 μm or less, more preferably 25 μm or less, more preferably 20 μm or less, particularly preferably 15 μm or less, and can also be 12 μm or less. By limiting the thickness of the intermediate layer, there is a tendency to improve impact resistance. In addition, the intermediate layer with limited thickness can well cope with the requirements of thinning and lightweighting.

[0153] <Release liner>

[0154] As a release liner for protecting or supporting the adhesive layer (which can be a release liner having both the function of protection and support.), its material and composition are not particularly limited, and an appropriate one can be selected from known release liners for use. For example, a release liner having a composition in which a release treatment (typically a release treatment layer based on a release treatment agent) is applied to at least one surface of the substrate can be appropriately used. As a substrate (release treatment object) constituting such a release liner, the same substrate (various plastic films, paper, cloth, rubber sheets, foam sheets, metal foils, their composites, etc.) as described above as the substrate constituting the adhesive sheet can be appropriately selected and used. As a release treatment agent forming the above-mentioned release treatment layer, a known or commonly used release treatment agent (for example, release treatment agents such as silicone, fluorine, and long-chain alkyl) can be used. In addition, a low-adhesive substrate formed of a fluorine-based polymer (e.g., polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, chlorofluoroethylene-vinylidene fluoride copolymer, etc.) or a low-polarity polymer (e.g., olefin resins such as polyethylene and polypropylene, etc.) can be used as a release liner without subjecting the surface of the substrate to a release treatment. Alternatively, a substrate having a low-adhesive surface subjected to a release treatment can be used as a release liner.

[0155] The thickness of the substrate and release treatment layer constituting the release liner is not particularly limited and can be appropriately selected according to the purpose, etc. The total thickness of the release liner (for a release liner having a release treatment layer on the surface of the substrate, the thickness of the entire substrate and the release treatment layer) is preferably about 15 μm or more (typically about 15 μm to 500 μm), and more preferably about 25 μm to 500 μm.

[0156] <Method for producing double-sided adhesive sheet>

[0157] In the preparation of double-sided adhesive sheet, the method for setting adhesive layer on one side and the other side of intermediate layer is not particularly limited. It is usually preferred that any method selected from the following is applied to the above-mentioned one side and the other side respectively: (1) adhesive composition is given (typically coated) to release liner and dried, thereby forming adhesive layer on the release liner, the adhesive layer is attached to the intermediate layer and the method for transfer (lamination) (hereinafter also referred to as "transfer method");And (2) adhesive composition is directly given (typically coated) to the intermediate layer and the method for drying (hereinafter also referred to as "direct coating method" or "direct method".). For example, transfer method can be applied to the double-sided application of intermediate layer to manufacture double-sided adhesive sheet (transfer-transfer method), or transfer method can be applied to one side of intermediate layer (typically the face where adhesive layer is initially set) and direct coating method is applied to the other side to manufacture double-sided adhesive sheet (transfer-direct method). In addition, by adopting (3) a method of applying the first adhesive composition (e.g., an adhesive composition for forming the first adhesive layer) to a release liner, applying an intermediate layer forming material (e.g., an aqueous dispersion of a resin) thereon, and further applying the second adhesive composition (e.g., an adhesive composition for forming the second adhesive layer) thereon, and then drying or curing the entirety (also referred to as simultaneous coating), a double-sided adhesive sheet having a first adhesive layer, an intermediate layer, and a second adhesive layer in sequence can be manufactured. According to the above method, the drying and curing treatment steps can be performed once for the entirety, and such an operation is advantageous in terms of productivity. In the technology disclosed herein, since a water-dispersible material is used as the intermediate layer forming material, it is not easy to produce intermixing of the layers (the components of one layer enter the area of ​​another layer), and an adhesive sheet can be manufactured by a simultaneous coating method of continuously coating the materials for forming the first adhesive layer, the intermediate layer, and the second adhesive layer. As the above-mentioned simultaneous coating method and conditions, various methods and conditions that are not easy to produce intermixing can be selected.

[0158] <Characteristics of Double-Sided Adhesive Sheets>

[0159] Although not particularly limited, the Young's modulus of the double-sided adhesive sheet can be in the range of 1.5 to 1500 MPa as in the middle layer. Here, the Young's modulus of the double-sided adhesive sheet is the Young's modulus of the unit cross-sectional area of ​​the middle layer as described in the embodiments described later, which is substantially consistent with the Young's modulus of the middle layer. Therefore, the Young's modulus of the middle layer can be estimated by the Young's modulus of the double-sided adhesive sheet converted into the value of the unit cross-sectional area of ​​the middle layer. The Young's modulus of the double-sided adhesive sheet can be less than 1000 MPa, less than 500 MPa, less than 300 MPa, less than 100 MPa, or less than 50 MPa. By making the Young's modulus of the double-sided adhesive sheet less than the above-mentioned upper limit, there is a tendency to improve impact resistance. In some ways, the Young's modulus of the double-sided adhesive sheet is less than 100MPa, preferably less than 50MPa, more preferably less than 30MPa, more preferably less than 25MPa, less than 20MPa, less than 15MPa, less than 10MPa, or less than 5MPa (for example, less than 5MPa). In addition, from the viewpoint of processability, the Young's modulus of the double-sided adhesive sheet can be more than 3MPa, more than 8MPa, more than 12MPa, or more than 15MPa. In some ways, the Young's modulus of the double-sided adhesive sheet is more than 30MPa, more than 50MPa, more than 75MPa, more than 150MPa, more than 400MPa, or more than 800MPa. Specifically, the Young's modulus of the double-sided adhesive sheet is measured by the method described in the embodiments described later.

[0160] The adhesive force of the double-sided adhesive sheet disclosed herein is not particularly limited. In some embodiments, the double-sided adhesive sheet is attached to a stainless steel plate and maintained at 23°C, 50% RH for 30 minutes. The 180-degree peel strength (peel strength to SUS plate) can be, for example, 5N / 20mm or more. The double-sided adhesive sheet showing this characteristic is preferably used as a strong adhesive double-sided adhesive sheet for firmly fixing articles and components. The above-mentioned peel strength to the SUS plate is preferably 6N / 20mm or more, and can also be 7N / 20mm or more. In some preferred embodiments, the above-mentioned peel strength to the SUS plate is 8N / 20mm or more, more preferably 10N / 20mm or more, further preferably 12N / 20mm or more, particularly preferably 14N / 20mm or more, and can also be 16N / 20mm or more. The upper limit of the above-mentioned peel strength to the SUS plate is not particularly limited, and can be about 30N / 20mm or less (for example, 25N / 20mm or less). The above-mentioned peel strength to the SUS plate can be specifically measured by the method described in the embodiments described later. In addition, in a double-sided PSA sheet having adhesive surfaces on both sides, the peel strength against the SUS plate of each side may be the same or different.

[0161] <Purpose>

[0162] The double-sided adhesive sheet disclosed herein is thin and can take into account both processability and impact resistance. Effectively utilizing this feature, the double-sided adhesive sheet disclosed herein can be pasted on various products that are expected to be thin and require processability and impact resistance, and the components constituting the products, and is preferably used for the fixing, joining, molding, decoration, protection, support and other purposes of the products or components. Among them, it can be preferably used for the fixing of the above-mentioned products and the above-mentioned components. For example, portable electronic devices have strong requirements for miniaturization and lightweight, and it is expected that the adhesive sheet for portable electronic devices is thin. In addition, portable electronic devices have the danger of falling due to their use form, and the adhesive sheet used in portable electronic devices will require impact resistance. Furthermore, the adhesive sheet used in the fixing of the components of portable electronic devices is processed into a shape suitable for the bonding and fixing part by implementing cutting processing such as punching processing, so it is required to have good processability. For such portable electronic devices, the double-sided adhesive sheet disclosed herein is suitable.

[0163] Non-limiting examples of the portable electronic devices include mobile phones, smart phones, tablet personal computers, notebook personal computers, various wearable devices (for example, wristband type worn on the wrist like a watch, modular type worn on a part of the body with a clip, a strap, etc., eye-wearing devices including glasses type (monocular type, binocular type. Also including head-mounted type.), clothing type worn on a shirt, socks, hat, etc. as an accessory, earmuff type installed on the ear like headphones, etc.), digital cameras, digital video cameras, audio equipment (portable music players, IC recorders, etc.), calculators (desk calculators, etc.), portable game devices, electronic dictionaries, electronic notebooks, electronic books, car-mounted information equipment, mobile radios, mobile televisions, mobile printers, mobile scanners, mobile modems, etc. It should be noted that in this specification, "portable" does not mean that it is sufficient to be able to be carried, but also means that it has a level of portability that an individual (a standard adult) can carry relatively easily.

[0164] The matters disclosed in this specification include the following.

[0165] [1] A double-sided adhesive sheet comprising, in this order, a first adhesive layer, at least one intermediate layer, and a second adhesive layer.

[0166] The total thickness of the double-sided adhesive sheet is 60 μm or less.

[0167] The thickness ratio of the intermediate layer is in the range of 10% to 60% relative to the total thickness.

[0168] The intermediate layer is formed of a water-dispersible material.

[0169] The Young's modulus of the intermediate layer is within a range of 1.5 to 1500 MPa.

[0170] [2] The double-sided adhesive sheet according to [1] above, wherein the storage modulus of the intermediate layer at a temperature of 25° C. and a frequency of 160 Hz is within 7.0×10 6 ~5.0×10 9 Within the range of Pa.

[0171] [3] The double-sided adhesive sheet according to [1] or [2], wherein the storage modulus of the intermediate layer at a temperature of 25° C. and a frequency of 1000 to 10000 Hz is 3.7×10 9 Below Pa.

[0172] [4] The double-sided PSA sheet according to any one of [1] to [3] above, wherein the intermediate layer comprises a polyurethane resin, a rubber, a polyolefin resin, an acrylic resin, or a blend thereof.

[0173] [5] The double-sided PSA sheet according to any one of [1] to [4] above, wherein both the first PSA layer and the second PSA layer are formed from a water-dispersible PSA composition.

[0174] [6] The double-sided PSA sheet according to any one of [1] to [5] above, wherein both the first PSA layer and the second PSA layer are acrylic PSA layers containing an acrylic polymer.

[0175] [7] The double-sided pressure-sensitive adhesive sheet according to [6] above, wherein the acrylic polymer has a glass transition temperature of -25°C or less.

[0176] [8] The double-sided PSA sheet according to any one of [1] to [7] above, wherein the 180-degree peel strength relative to a stainless steel plate is 6 N / 20 mm or more.

[0177] [9] The double-sided pressure-sensitive adhesive sheet according to any one of [1] to [8] above, which is used for fixing components in a portable electronic device.

[0178] Example

[0179] Hereinafter, some examples related to the present invention will be described, but the present invention is not intended to be limited to the contents shown in the examples. It should be noted that in the following description, "parts" and "%" are weight references unless otherwise specified.

[0180] <Example 1>

[0181] (Preparation of acrylic polymer)

[0182] In a reaction vessel equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a reflux condenser, 0.07 parts of a reactive surfactant (trade name "Aqualon KH-1025", manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and 61.1 parts of distilled water were added, and nitrogen substitution was performed at 60° C. for 1 hour while stirring. Then, 0.10 parts of a polymerization initiator (trade name "VA-057", manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added thereto. Emulsion polymerization was carried out while 85 parts of 2-ethylhexyl acrylate (2EHA), 13 parts of methyl acrylate (MA), 1.25 parts of acrylic acid (AA), 0.75 parts of methacrylic acid (MAA), 0.025 parts of tert-dodecyl mercaptan (chain transfer agent), 0.02 parts of 3-methacryloxypropyltrimethoxysilane (trade name "KBM-503", manufactured by Shin-Etsu Chemical Co., Ltd.) and 1.93 parts of the above-mentioned reactive surfactant were slowly added dropwise at 60° C. for 4 hours. After keeping at 60° C. for 3 hours, 0.05 parts of the above-mentioned polymerization initiator was added, and the temperature was kept at 60° C. for another 2 hours. The system was cooled to room temperature, and pH was adjusted to 7 using 10% ammonia water as a pH adjuster, and 0.0072 parts of a preservative (trade name "Neosintle 2208", manufactured by SC Environmental Science Co., Ltd.) was added. Thus, an aqueous dispersion of an acrylic polymer was prepared. The solid content concentration of the acrylic polymer was 50.5%, and the sol weight average molecular weight (Mw) was 340,000.

[0183] (Preparation of Adhesive Composition)

[0184] In the aqueous dispersion of the acrylic polymer, 30 parts of a tackifier resin (polymerized rosin ester, trade name "SUPERESTER E-865NT", manufactured by Arakawa Chemical Industries, Ltd., softening point 160°C) and 3 parts of polyacrylic acid (trade name "ARON A-10", manufactured by Toagosei Co., Ltd., number average molecular weight (Mn): 250000) were added to 100 parts of the solid content of the aqueous dispersion, and 2 parts of a leveling agent (trade name "PELEX OT-P", manufactured by Kao Corporation) were further added. Then, the pH was adjusted to 8 with 10% ammonia water to prepare an adhesive composition.

[0185] (Formation of Adhesive Layer)

[0186] The adhesive composition obtained as described above was applied to the silicone-treated surface of a 38 μm thick polyethylene terephthalate (PET) release liner (trade name "DIAFOIL MRF38", manufactured by Mitsubishi Chemical Corporation) so that the thickness after drying was 10 μm. Then, it was heated and dried at 100° C. for 3 minutes to form an adhesive layer on the release liner.

[0187] (Formation of Intermediate Layer A)

[0188] A thickener (trade name "Adekanol UH-541VF", manufactured by ADEKA Corporation) was added to a polyurethane resin (polyester skeleton) aqueous dispersion (trade name "UCOAT DA-100", manufactured by Sanyo Chemical Co., Ltd.) in such a way that the viscosity of the coating liquid after addition becomes 3.0 Pa·s. Furthermore, 1 part of a leveling agent (trade name "PELEX OT-P", manufactured by Kao Corporation) was added. The obtained coating liquid (composition for forming an intermediate layer) was applied to the silicone-treated surface of a PET release liner (trade name "DIAFOIL MRF38", manufactured by Mitsubishi Chemical Corporation) having a thickness of 38 μm in such a way that the thickness after drying becomes 10 μm. Then, the intermediate layer A (intermediate layer film) of this example was prepared by heating and drying at 100°C for 3 minutes.

[0189] (Preparation of double-sided adhesive sheet)

[0190] One side (exposed side) of the adhesive layer was bonded to one side of the intermediate layer A. Next, the release liner was removed, and another adhesive layer was bonded to the other side of the intermediate layer A to obtain a laminate having a total thickness of 30 μm with a structure of the first adhesive layer / intermediate layer A / second adhesive layer. The laminate was treated in an autoclave at 50° C. and 5 atm for 15 minutes, and then aged in a dryer at 50° C. overnight to prepare the double-sided adhesive sheet of this example.

[0191] <Examples 2~6>

[0192] Intermediate layers B to F were prepared in the same manner as in Example 1 except that the water-dispersible material used in forming the intermediate layer was changed to the material shown below. Double-sided PSA sheets of each example were obtained in the same manner as in Example 1 except that any one of the intermediate layers B to F was used as the intermediate layer.

[0193] Intermediate layer B: water-dispersible polyurethane resin (ester skeleton) (trade name "ADEKA BONTIGHTER HUX-380", manufactured by ADEKA Corporation)

[0194] Intermediate layer C: water-dispersible polyurethane resin (aromatic isocyanate skeleton) (trade name "SUPERFLEX 830HS", manufactured by Daiichi Kogyo Seiyaku Co., Ltd.)

[0195] Intermediate layer D: water-dispersible polyolefin resin (ionomer) (trade name "CHEMIPEARL SA100M", manufactured by Mitsui Chemicals, Inc.)

[0196] Intermediate layer E: water-dispersible polyurethane resin (ether skeleton) (trade name "ADEKA BONTIGHTER HUX-282", manufactured by ADEKA Corporation)

[0197] Intermediate layer F: A polyurethane / silica blend prepared by adding 40 parts (based on solid content) of an aqueous dispersion of silica particles (trade name "SNOWTEX ST-50T", manufactured by Nissan Chemical Co., Ltd.) to 100 parts of the solid content of a water-dispersible polyurethane resin (ester skeleton) (trade name "ADEKA BONTIGHTER HUX-380", manufactured by ADEKA Co., Ltd.), and stirring and mixing the mixture.

[0198] Intermediate layer G: an acrylic / urethane blend prepared by mixing the adhesive composition of Example 1 with an aqueous dispersion of a polyurethane resin (polyester skeleton) (trade name "UCOAT DA-100", manufactured by Sanyo Chemical Co., Ltd.) at a ratio of 2:1 based on solid content.

[0199] <Examples 7~10>

[0200] The thickness of the intermediate layer and the total thickness of the double-sided PSA sheet were changed as shown in Table 1. The double-sided PSA sheets of each example were obtained in the same manner as in any of Examples 1 to 3. The thickness of each PSA layer in the double-sided PSA sheet of each example was (total thickness - intermediate layer thickness) × 1 / 2.

[0201] <Examples 11~15>

[0202] The double-sided PSA sheets of various examples were obtained by changing the configuration of the double-sided PSA sheets as shown in Table 2.

[0203] <Evaluation>

[0204] [Young's modulus]

[0205] For the intermediate layer material, for samples that are relatively hard and can support themselves in a thin film, cut them out with a TD (transverse direction) of 10 mm and a MD (machine direction) of 50 mm. For samples that are soft, sticky, and cannot support themselves, cut them out with a MD of 30 mm and a TD of 2.5 mm in cross-sectional area (thickness × TD) in the same way as the evaluation method for conventional adhesives. 2 The length of about 10 mm is cut out and rolled into a rod along TD to obtain a sample. The obtained sample is fixed to a tensile testing machine with a device chuck in a manner that the effective length is 10 mm. After being placed in a measuring atmosphere at 23°C for 2 minutes, a tensile test is performed at a tensile speed of 50 mm / min to obtain a stress (vertical axis)-strain (horizontal axis) curve. Five points in the micro-deformation area (within 5% strain) are selected from the obtained stress-strain curve, and the Young's modulus [MPa] of the intermediate layer is obtained by the slope obtained by the linear approximation formula. As a tensile testing machine, a precision universal testing machine Autograph AG-IS (manufactured by Shimadzu Corporation) or its equivalent is used.

[0206] It should be noted that regarding the Young's modulus of the double-sided PSA sheet with an intermediate layer, since the Young's modulus of the PSA layer is extremely small compared to the Young's modulus of the intermediate layer, the value converted to the cross-sectional area per unit cross-sectional area of ​​the intermediate layer is used, not the cross-sectional area of ​​the double-sided PSA sheet including the PSA layer.

[0207] [Storage modulus]

[0208] The intermediate layer or adhesive layer of each example was punched out to a length of 10 mm in TD and 70 mm in MD to produce a strip-shaped sample. For materials that are sticky and cannot support themselves, a strip-shaped sample was punched out to a length of 2.5 mm in cross-sectional area. 2 The obtained sample was rolled into a cylindrical shape in a left-right manner. The device chuck was fixed to the obtained sample so that the effective measurement length of the measuring jig was 20 mm, and the dynamic viscoelasticity measurement was performed using a dynamic viscoelasticity tester (manufactured by TA Instruments Japan, model name "RSA-G2") under the following conditions.

[0209] (Measurement conditions)

[0210] Measurement mode: Tensile

[0211] Measuring frequency: 1Hz

[0212] Temperature range: -40℃~30℃

[0213] Heating rate: 5℃ / min

[0214] The measurements were performed in the elastic deformation region.

[0215] The frequency dependency data at each temperature were obtained by using the analysis software provided by TA Instruments, with the reference temperature set to 25°C and the frequency dependency data at other temperatures shifted to obtain the frequency dependency data of the storage modulus (called a master curve in the polymer field).

[0216] The storage modulus [Pa] at a reference temperature of 25° C. and at each frequency (160 Hz, 1000 Hz, and 10000 Hz) was determined from the obtained frequency dependency data of the storage modulus.

[0217] [Peel strength to SUS plate]

[0218] The peel strength of the double-sided adhesive sheet of each example to the SUS plate was measured as follows. That is, the release liner covering one side of the double-sided adhesive sheet was peeled off and attached to a PET film with a thickness of 25 μm for backing. The adhesive sheet of the backing was cut into a size of 20 mm in width and 100 mm in length to make a test piece. Under an environment of 23°C and 50% RH, a 2kg roller was moved back and forth once to crimp the test piece to a stainless steel plate (SUS304BA plate) as an adherend. After keeping it under an environment of 23°C and 50% RH for 30 minutes, the 180-degree peel strength [N / 20mm] was measured using a tensile testing machine at a tensile speed of 300 mm / min according to JIS Z0237. The measurement was performed 3 times (i.e., N=3), and their average value was set as the peel strength of the adhesive sheet to the SUS plate.

[0219] [Impact resistance]

[0220] The double-sided adhesive sheet with the adhesive surface protected by the release liner is punched into a frame shape of 24.5mm square with a width of 2mm to obtain a frame-shaped adhesive sheet. In addition, a stainless steel plate (SUS304BA) with a 20mm square hole and a stainless steel plate (SUS304BA) with a thickness of 3mm and a 25mm square square are prepared in the central part of a square with a thickness of 2mm and an outer shape of 50mm square. The frame-shaped adhesive sheet with the release liner removed is configured between the above two stainless steel plates in a manner that the above two stainless steel plates and the frame-shaped adhesive sheet are point-symmetrically configured from the center (configured in a manner that surrounds the hole of the perforated stainless steel plate), and the pressure is evenly applied under the conditions of 62N and 10 seconds. After standing for 30 minutes at 80°C, it returns to 23°C overnight. It is set as a test piece. A cylindrical measuring table with a length of 50 mm, an outer diameter of 49 mm, and an inner diameter of 43 mm is set on the base of a DuPont impact tester (manufactured by Toyo Seiki Seisaku-sho, Ltd.), and a test piece is placed on it with a square stainless steel plate as the lower side in a point-symmetrical arrangement from the center of the measuring table. The test piece is arranged in a manner that the perforated stainless steel plate on the upper side is supported by the measuring table, and the square stainless steel plate on the lower side enters the hollow part in the above-mentioned measuring table in a state where it is bonded to the perforated stainless steel plate by the above-mentioned frame-shaped adhesive sheet. A stainless steel striking core with a front end radius of 3.1 mm is placed on the test piece (specifically, the square stainless steel plate on the lower side), and a weight is dropped onto the striking core (impact type) at 23°C and 50% RH under the following conditions (weight of the weight and drop height). That is, for the weight of the falling weight and the falling height, when the weight is 50g, the falling height varies in the range of 50mm to 500mm in units of 50mm; when the weight is 100g, the falling height varies in the range of 300mm to 500mm in units of 50mm; when the weight is 150g, the falling height varies in the range of 350mm to 500mm in units of 50mm; when the weight is 200g, the falling height varies in the range of 400mm to 500mm in units of 50mm; when the weight is 300g, the falling height varies in the range of 350mm to 500mm in units of 50mm, so that the energy gradually increases until peeling occurs. At this time, the energy that has been measured is not tested, and the load and height are set in a way that the energy is not repeated. The accumulated energy until the previous condition of peeling is set as the impact absorption energy (J). The energy is calculated by load × height. The measurement was performed three times (ie, N=3), and the average value thereof was used as the evaluation result of the impact resistance.

[0221] [Processability (punching processability)]

[0222] For each example of double-sided adhesive sheet with release liner (double-sided adhesive sheet with two release liners protecting each adhesive surface), 5 strip test pieces with TD30mm and MD150mm were cut out. For the above-mentioned strip test pieces, a punch (trade name "Power Punch (Japanese name: Power Punch) DP-110", MAX Co., Ltd.) was used to continuously punch each strip test piece along MD with 20 shots per time, and the number of continuous punching was measured and evaluated according to the following criteria.

[0223] (Number of continuous punching)

[0224] 91 times or more: ◎

[0225] 81-90 times: ○

[0226] 71-80 times: △

[0227] Less than 70 times: ×

[0228] Prior to this evaluation (processability evaluation), only one release liner of the double-sided PSA sheet with a release liner was changed from trade name "DIAFOIL MRF38" to trade name "DIAFOIL MHA25" (release liner manufactured by Mitsubishi Chemical Corporation), and punching was performed from the DIAFOIL MHA25 side.

[0229] The summary and evaluation results of each example are shown in Tables 1 and 2.

[0230] [Table 1]

[0231]

[0232] [Table 2]

[0233]

[0234] As shown in Tables 1 to 2, the double-sided adhesive sheets of Examples 1 to 10 having an intermediate layer with a Young's modulus of 1.5 to 1500 MPa have an impact resistance as high as 0.1 J or more, and excellent processability. On the other hand, in Example 11 using an intermediate layer with a Young's modulus exceeding 1500 MPa, a result of impact resistance as low as 0.008 J was obtained. In addition, in Example 13 using an intermediate layer with a Young's modulus of less than 1.5 MPa, the evaluation result of processability was unqualified. In addition, in the adhesive sheet of Example 14 using the same intermediate layer material as Example 1 and having a thickness ratio of the intermediate layer relative to the total thickness greater than 60%, a result of impact resistance as low as 0.02 J was obtained. The thickness ratio of the intermediate layer of the adhesive sheets of Examples 12 and 15, which are formed only by the adhesive layer without an intermediate layer, is 0%, and the Young's modulus of the adhesive layer itself is as low as 0.06 MPa, and the evaluation result of processability is unqualified.

[0235] It should be noted that the measurement results of the Young's modulus of the PSA sheets of Examples 1 and 3 were both within the range of 1.5 to 1500 MPa, confirming a predetermined correlation with the Young's modulus of the intermediate layer.

[0236] The PSA sheets of Examples 12 and 15 (PSA sheets consisting of only the PSA layer without an intermediate layer) had a Young's modulus of 0.06 MPa and a storage modulus of 2.9×10 6 Pa, 10 3 The storage modulus at Hz is 8.0×10 6 Pa, 10 4 The storage modulus at Hz is 6.0×10 7 Pa.

[0237] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the claims. The aspects described in the claims include aspects obtained by variously modifying and changing the specific examples described above.

[0238] Description of Reference Numerals

[0239] 1 Double-sided adhesive sheet

[0240] 11. 1st adhesive layer

[0241] 11A 1st adhesive surface

[0242] 12 Second adhesive layer

[0243] 12A Second adhesive surface

[0244] 15 Middle Layer

[0245] 21 Release liner

Claims

1. A double-sided adhesive sheet comprising, in order, a first adhesive layer, at least one intermediate layer, and a second adhesive layer, The total thickness of the double-sided adhesive sheet is 60 μm or less. The thickness ratio of the intermediate layer is in the range of 10% to 60% relative to the total thickness. The intermediate layer is formed of a water-dispersible material, The Young's modulus of the intermediate layer is in the range of 1.5 to 1500 MPa.

2. The double-sided adhesive sheet according to claim 1, wherein The storage modulus of the intermediate layer at a temperature of 25°C and a frequency of 160 Hz is 7.0×10 6 ~5.0×10 9 Within the range of Pa.

3. The double-sided adhesive sheet according to claim 1 or 2, wherein The storage modulus of the intermediate layer at a temperature of 25°C and a frequency of 1000 to 10000 Hz is 3.7×10 9 Below Pa.

4. The double-sided adhesive sheet according to claim 1 or 2, wherein The intermediate layer comprises polyurethane resin, rubber, polyolefin resin, acrylic resin or a blend thereof.

5. The double-sided adhesive sheet according to claim 1 or 2, wherein The first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer are both formed from a water-dispersible pressure-sensitive adhesive composition.

6. The double-sided adhesive sheet according to claim 1 or 2, wherein Both the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer are acrylic pressure-sensitive adhesive layers containing an acrylic polymer.

7. The double-sided adhesive sheet according to claim 6, wherein The acrylic polymer has a glass transition temperature of -25°C or lower. 8 . The double-sided adhesive sheet according to claim 1 , which has a 180-degree peel strength with respect to a stainless steel plate of 6 N / 20 mm or more. 9 . The double-sided pressure-sensitive adhesive sheet according to claim 1 or 2, which is used for fixing components in portable electronic devices.

Citation Information

Patent Citations

  • Pressure-sensitive adhesive sheet and its production

    JP2000248236A

  • Optical member with pressure-sensitive adhesive and method for producing the same and image display device

    JP2006063189A

  • Adhesive composition, pressure sensitive adhesive double coated tape, adhesion method and portable electronic device

    JP2007051271A

  • double sided adhesive tape

    JP2009536675A

  • Adhesive tape and manufacturing method therefor

    JP2017105878A